Crystal of dihydropyridone derivative or solvate thereof
By studying the specific crystal type of dihydrial pyrine derivatives, the problems that existing drugs fail to be met in the treatment of obesity and side effects when treating obesity, realize the high biological utilization and purity of the drug, optimize the crystal development of the drug development, Type selection.
Patent Information
- Application Number
- CN202380046447.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-24
AI Technical Summary
When existing drugs treat obesity, the efficacy and side effects are not met. At the same time, the crystal form of dihydropyridone derivatives has an important impact on the bioavailability and purity of the drug, but it is difficult to predict the original medicinal crystal form with good physical properties. .
Studies and found a specific crystal type of dihydrial hydrogen pyrine derivatives, including water -free and aquarmers crystals, which have stability and good purity and solubility, and are suitable for drug raw materials.
By preparing these specific crystal forms, the bioavailability of the drug and the purity of the original drug are improved, the efficacy and side effects of existing drugs in the treatment of obesity are solved, and the selection of crystal forms in drug development is optimized.
Smart Images

Figure CN119365463A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a crystal of a dihydropyridone derivative or a solvate (preferably a hydrate) thereof and a pharmaceutical composition containing the same. Background Art
[0002] Obesity is defined as a state of excess body fat or adipose tissue relative to body weight and is considered a major risk factor for health problems. Body mass index (BMI) is a simple index of height-to-weight ratio commonly used when classifying groups or individuals of adults (over 15 years old) as overweight or obese. It is defined as the weight in kilograms divided by the square of the height in meters (kg / m 2 ). The World Health Organization defines BMI as 25 kg / m 2 Above is considered as "overweight", 30kg / m 2 The above is considered "obesity". On the other hand, the Japanese Society of Obesity defines BMI as 25 kg / m 2 The above is considered "obesity". This is because the number of obesity-related diseases including diabetes and dyslipidemia increases with BMI, and the average number of these diseases is at a BMI of 25 kg / m 2 It will become above 1.0. According to a survey conducted by the World Health Organization in 2005, about 1.6 billion people in the world are overweight, and at least 400 million people are obese. Obesity is mainly caused by the increase in the proportion of calorie intake relative to physical activities and consumption in daily life. In recent years, due to the increase in the intake of high-fat and high-sugar foods, the number of obese people has increased. It is predicted that in 2015, more than 700 million people in the world will be diagnosed with obesity. For the treatment of these, diet therapy, exercise therapy, drug therapy, etc. are carried out. Drugs such as orlistat, mazindol, and sibutramine are used in drug therapy, but they are not satisfactory in terms of both efficacy and side effects.
[0003] One of the causes of obesity is excessive intake of neutral fat. Neutral fat (triglyceride) ingested through diet is decomposed into 2-monoacylglycerol and free fatty acids by pancreatic lipase in the digestive tract and absorbed by intestinal epithelial cells. The acyl group of free fatty acids is transferred to 2-monoacylglycerol by monoacylglycerol acyltransferase (MGAT). The generated diacylglycerol is further converted to neutral fat by diacylglycerol acyltransferase (DGAT).
[0004] Three isoforms of MGAT have been identified: MGAT1, MGAT2, and MGAT3. Among them, MGAT2 and MGAT3 are highly expressed in the small intestine and are believed to be involved in fat absorption in the small intestine. It has been reported that experiments conducted using MGAT2 knockout mice showed that the expression of MGAT2 in the small intestine was increased due to high-fat diet load, and MGAT activity increased (Non-Patent Document 1). Furthermore, it was confirmed that in MGAT2 knockout mice, weight gain due to high-fat diet load was suppressed, the induction of insulin resistance was suppressed, the increase in blood cholesterol was suppressed, the formation of fatty liver was suppressed, and energy consumption was increased (Non-Patent Document 2).
[0005] Patent Documents 1 and 2 describe the formula: The dihydropyridone derivatives have MGAT2 inhibitory activity and are useful for the treatment and / or prevention of diseases in which MGAT2 is involved. In addition, the following compounds are disclosed in the Examples of Patent Documents 1 and 2: However, the crystal of this compound is not disclosed. Background Art Literature Patent Literature
[0006] Patent Document 1: International Publication No. WO2019 / 013311 Patent Document 2: International Publication No. WO2019 / 013312 Non-patent literature
[0007] Non-patent document 1: Journal of Biological Chemistry (2004), 279, 18878-18886 Non-patent document 2: Nature Medicine (2009), 15, (4), 442-446 Summary of the invention Problems to be solved by the invention
[0008] Pharmaceutical active ingredients have substantially different physical properties depending on their respective solid forms. Such differences in physical properties may affect, for example, the method for producing or administering the pharmaceutical active ingredient, or a pharmaceutical composition containing the pharmaceutical active ingredient. Compared to other solid forms, the present invention provides crystals of dihydropyridone derivatives or solvates thereof that are very useful in the method for producing or administering the pharmaceutical active ingredient, or a pharmaceutical composition containing the pharmaceutical active ingredient. Generally, the physical properties of the crystals of useful compounds for drugs have a great impact on the bioavailability of the drug, the purity of the original drug, the prescription of the preparation, etc., so it is very important in drug development. In addition, since these physical properties depend on the properties of each compound, it is usually difficult to predict the crystal form of the original drug with good physical properties, and various studies are required for each compound. In particular, the compounds recorded in Patent Documents 1 and 2 have a tendency to reduce solubility if crystallized. Therefore, it is necessary to study which crystal form of the compounds described in Patent Documents 1 and 2, especially the compounds useful as medicines, has good solubility and is optimal as a medicine. Solution to the problem
[0009] After intensive research, the present inventors found that the specific crystal form of the compound represented by formula (I) or (II) is stable and has good purity and / or solubility. The present invention relates to the following. [1] An anhydrate crystal and / or hydrate crystal of a compound represented by formula (I), which is the following formula (I): The represented compounds are anhydrate crystals and / or hydrate crystals having a water content not more than that of 0.25 hydrate. [2] The hydrate crystal according to [1], wherein the water content is less than the water content equivalent to 0.25 hydrate. [3] The hydrate crystal according to [2], which has peaks at diffraction angles (2θ) of 13.0°±0.2°, 18.4°±0.2°, 20.0°±0.2°, 20.4°±0.2° and 23.7°±0.2° in its powder X-ray diffraction pattern. [4] The hydrate crystals according to [3], which have peaks at diffraction angles (2θ) of 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.4±0.2°, 18.4°±0.2°, 19.3°±0.2°, 20.0°±0.2°, 20.4°±0.2°, 21.4°±0.2°, 23.7°±0.2° and 24.1±0.2° in the powder X-ray diffraction pattern. [5] A 0.25 hydrate crystal as described in [1]. [6] The 0.25 hydrate crystals as described in [5], which have peaks at diffraction angles (2θ) of 13.0°±0.2°, 18.4°±0.2°, 19.9°±0.2°, 20.5°±0.2° and 23.7°±0.2° in the powder X-ray diffraction pattern. [7] The 0.25 hydrate crystals as described in [6], which have peaks at diffraction angles (2θ) of 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.5±0.2°, 18.4°±0.2°, 19.2°±0.2°, 19.9°±0.2°, 20.5°±0.2°, 21.5°±0.2°, 23.7°±0.2° and 24.2°±0.2° in the powder X-ray diffraction pattern. [8] The anhydrate crystals as described in [1], which have peaks at diffraction angles (2θ) of 13.1°±0.2°, 18.3°±0.2°, 20.2°±0.2°, 20.5°±0.2° and 23.8°±0.2° in the powder X-ray diffraction pattern. [9] The anhydrate crystals as described in [8], which have peaks at diffraction angles (2θ) of 13.1°±0.2°, 15.6°±0.2°, 16.7°±0.2°, 17.1±0.2°, 18.3°±0.2°, 19.5°±0.2°, 20.2°±0.2°, 20.5°±0.2°, 21.5°±0.2° and 23.8°±0.2° in the powder X-ray diffraction pattern.
[10] The crystal as described in [1], wherein when the crystal is left to stand at a temperature of 25°C and a relative humidity of 35%, and a powder X-ray diffraction experiment is performed under the same environment, the crystal has a peak at the diffraction angle described in [3] or [4]; The crystal is allowed to stand at a temperature of 25° C. and a relative humidity of 60%, and when a powder X-ray diffraction experiment is conducted under the same environment, a peak is found at the diffraction angle described in [6] or [7]; or The crystals were allowed to stand at a temperature of 50°C and a relative humidity of 25%, and a powder X-ray diffraction experiment was performed under the same environment. A peak was found at the diffraction angle described in [8] or [9].
[11] The crystal according to [1], which has a melting point of 236 to 237°C.
[12] The crystal according to [1], which has a melting point of 236 to 237° C. as measured by differential scanning calorimetry (DSC) or simultaneous thermogravimetric and differential thermal analysis (TG / DTA).
[13] A hydrate crystal having the formula (I): The hydrate crystal of the compound represented by is a hydrate crystal, and the water content Y (weight %) is 0.0<Y≦1.5 weight %.
[14] A hydrate crystal of the compound represented by formula (I) according to [1], wherein the water content is not more than the water content equivalent to 0.25 hydrate, and the crystal density thereof is 0.1447 W / m2 at -60°C under CuKα line. When performing single crystal structure analysis, the crystallographic data has the following characteristics: Space group: P1 α=91.5±0.6° β=105.3±0.1° γ=91.7±0.6°.
[15] A 0.25 hydrate crystal of the compound represented by the formula (I) as described in [5], which has a CuKα line at -60°C. When performing single crystal structure analysis, the crystallographic data essentially have the following characteristics: Space group: P1 α=92.077(2)° β=105.324(3)° γ=92.281(3)°.
[16] The anhydrate crystals as described in [1], which are irradiated by CuKα at -60°C When performing single crystal structure analysis, the crystallographic data essentially have the following characteristics: Space group: P21 α=90° β=105.3090(10)° γ=90°.
[17] The crystal as described in [1], which has peaks at diffraction angles (2θ) of 13.05°±0.25°, 18.35°±0.25°, 20.05°±0.35°, 20.45°±0.25° and 23.75°±0.25° in its powder X-ray diffraction pattern.
[18] The crystal as described in
[17] , which has peaks at diffraction angles (2θ) of 13.05°±0.25°, 15.55°±0.25°, 16.65°±0.25°, 17.00°±0.30°, 18.35°±0.25°, 19.35°±0.35°, 20.05°±0.35°, 20.45°±0.25°, 21.45°±0.25° and 23.75°±0.25° in its powder X-ray diffraction pattern.
[19] The crystal as described in any one of [1] to
[18] , which has a Raman spectrum at 1448 cm-1 ±2cm -1 、1511cm -1 ±2cm -1 and 2885cm -1 ±2cm -1 Has an absorption peak.
[20] The crystal as described in
[19] , which has a Raman spectrum at 1448 cm -1 ±2cm -1 、1511cm -1 ±2cm -1 、1650cm -1 ±2cm -1 、2885cm -1 ±2cm -1 and 2947cm -1 ±2cm -1 Has an absorption peak.
[21] A crystal of a compound represented by formula (II),
[22] The crystal as described in
[21] , which has peaks at diffraction angles (2θ) of 16.3°±0.2°, 18.4°±0.2°, 20.4°±0.2°, 22.8°±0.2° and 23.9°±0.2° in its powder X-ray diffraction pattern.
[23] The crystal as described in
[22] , which has peaks at diffraction angles (2θ) of 15.1°±0.2°, 16.3°±0.2°, 18.4°±0.2°, 19.2°±0.2°, 20.4°±0.2°, 21.1°±0.2°, 22.0°±0.2°, 22.8°±0.2°, 23.3°±0.2° and 23.9°±0.2° in its powder X-ray diffraction pattern.
[24] The crystal as described in any one of
[21] to
[23] , which has a Raman spectrum at 577 cm -1 ±2cm -1 、612cm -1 ±2cm -1 、740cm -1 ±2cm -1 、1571cm -1 ±2cm -1 and 1718cm -1 ±2cm -1 Has an absorption peak.
[25] A pharmaceutical composition comprising the crystal according to any one of [1] to
[24] above.
[0010] [1A] An anhydrate crystal and / or hydrate crystal of a compound represented by formula (I), which is the following formula (I): The represented compounds are anhydrate crystals and / or hydrate crystals having a water content not more than that of 0.25 hydrate. [2A] The crystal according to [1A], which has peaks at diffraction angles (2θ) of 13.0°±0.2°, 18.4°±0.2°, 20.0°±0.2°, 20.4°±0.2° and 23.7°±0.2° in its powder X-ray diffraction pattern. [3A] The crystal as described in [2A], which has peaks at diffraction angles (2θ) of 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.4±0.2°, 18.4°±0.2°, 19.3°±0.2°, 20.0°±0.2°, 20.4°±0.2°, 21.4°±0.2°, 23.7°±0.2° and 24.1±0.2° in its powder X-ray diffraction pattern. [4A] The 0.25 hydrate crystal as described in [1A], which has peaks at diffraction angles (2θ) of 13.0°±0.2°, 18.4°±0.2°, 19.9°±0.2°, 20.5°±0.2° and 23.7°±0.2° in the powder X-ray diffraction pattern. [5A] The crystal as described in [4A], which has peaks at diffraction angles (2θ) of 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.5±0.2°, 18.4°±0.2°, 19.2°±0.2°, 19.9°±0.2°, 20.5°±0.2°, 21.5°±0.2°, 23.7°±0.2° and 24.2°±0.2° in its powder X-ray diffraction pattern. [6A] The anhydrate crystals as described in [1A], which have peaks at diffraction angles (2θ) of 13.1°±0.2°, 18.3°±0.2°, 20.2°±0.2°, 20.5°±0.2° and 23.8°±0.2° in the powder X-ray diffraction pattern. [7A] The crystal as described in [6A], which has peaks at diffraction angles (2θ) of 13.1°±0.2°, 15.6°±0.2°, 16.7°±0.2°, 17.1±0.2°, 18.3°±0.2°, 19.5°±0.2°, 20.2°±0.2°, 20.5°±0.2°, 21.5°±0.2° and 23.8°±0.2° in its powder X-ray diffraction pattern. [8A] A crystal of a compound represented by formula (II), [9A] The crystal as described in [8A], which has peaks at diffraction angles (2θ) of 16.3°±0.2°, 18.4°±0.2°, 20.4°±0.2°, 22.8°±0.2° and 23.9°±0.2° in its powder X-ray diffraction pattern. [10A] The crystal as described in [9A], which has peaks at diffraction angles (2θ) of 15.1°±0.2°, 16.3°±0.2°, 18.4°±0.2°, 19.2°±0.2°, 20.4°±0.2°, 21.1°±0.2°, 22.0°±0.2°, 22.8°±0.2°, 23.3°±0.2° and 23.9°±0.2° in its powder X-ray diffraction pattern. [11A] A pharmaceutical composition comprising the crystal according to any one of [1A] to [10A] above. Effects of the Invention
[0011] The crystal of the present invention is useful as a pharmaceutical raw material for the compound represented by formula (I) or (II). That is, a pharmaceutical composition containing the crystal of the present invention is very useful as a therapeutic agent or preventive agent for a disease in which MGAT2 is involved. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The figure shows the powder X-ray diffraction pattern of the 0.25 hydrate crystal of the compound represented by formula (I) (measurement conditions: temperature 25°C, relative humidity 60%). The horizontal axis shows 2θ (°), and the vertical axis shows intensity (Count). Figure 2 The powder X-ray diffraction pattern (measurement conditions: temperature 25°C, relative humidity 35%) of the hydrate crystal of the compound represented by formula (I) (containing X molecules of water per molecule of the compound represented by formula (I), but 0<X<0.25) is shown. The horizontal axis represents 2θ (°), and the vertical axis represents intensity (Count). Figure 3 The figure shows the powder X-ray diffraction pattern of the anhydrate crystal of the compound represented by formula (I) (measurement conditions: temperature 50°C, relative humidity 25%). The horizontal axis shows 2θ (°), and the vertical axis shows intensity (Count). Figure 4 The crystal structure (structure in the asymmetric unit) of the 0.25 hydrate crystal of the compound represented by formula (I) is shown. Figure 5A molecular structure diagram of the compound represented by formula (I) showing a 0.25 hydrate crystal of the compound represented by formula (I) (showing a molecule containing S1). Figure 6 A molecular structure diagram of the compound represented by formula (I) showing a 0.25 hydrate crystal of the compound represented by formula (I) (showing a molecule containing S2). Figure 7 A molecular structure diagram of the compound represented by formula (I) showing a 0.25 hydrate crystal of the compound represented by formula (I) (showing a molecule containing S3). Figure 8 A molecular structure diagram of the compound represented by formula (I) showing a 0.25 hydrate crystal of the compound represented by formula (I) (showing a molecule containing S4). Fig. 9 The crystal structure (structure in the asymmetric unit) of the anhydrate crystal of the compound represented by formula (I) is shown. Fig.10 A molecular structure diagram of the compound represented by formula (I) showing an anhydrate crystal of the compound represented by formula (I) (showing a molecule containing S1). Fig.11 A molecular structure diagram of the compound represented by formula (I) showing an anhydrate crystal of the compound represented by formula (I) (showing a molecule containing S2). Fig.12 The results of DSC analysis of the crystal of the compound represented by formula (I) obtained in Example 1 are shown. The vertical axis represents heat, and the horizontal axis represents temperature. Fig.13 The TG / DTA analysis results of the crystals of the compound represented by formula (I) obtained in Example 1 are shown. The vertical axis represents heat (μV) or weight change (%), and the horizontal axis represents temperature (°C). Cel in the figure means degrees Celsius (°C). Fig.14 The water adsorption / desorption isotherms of the crystals of the compound represented by formula (I) obtained in Example 1 are shown. The vertical axis represents the weight change (%) (Change In Mass), and the horizontal axis represents the relative humidity (%) (Target % P / P0). The curve drawn with diamonds is the water adsorption isotherm, and the curve drawn with squares is the water desorption isotherm. Fig.15 The powder X-ray diffraction pattern of the crystal of the compound represented by formula (II) is shown. The horizontal axis represents 2θ (°) and the vertical axis represents intensity (Count). Fig.16 The results of DSC analysis of the crystal of the compound represented by formula (II) are shown. The vertical axis represents heat and the horizontal axis represents temperature. Fig.17The TG / DTA analysis results of the crystals of the compound represented by formula (II) are shown. The vertical axis represents heat (μV) or weight change (%), and the horizontal axis represents temperature (°C). Cel in the figure means Celsius (°C). Fig.18 The moisture adsorption / desorption isotherm of the crystal of the compound represented by formula (II) is shown. The vertical axis represents the weight change (%) (Change In Mass), and the horizontal axis represents the relative humidity (%) (Target % P / P0). The curve drawn with a diamond is the moisture adsorption isotherm, and the curve drawn with a square is the moisture desorption isotherm. Fig.19 The peaks of the powder X-ray diffraction pattern of the 0.25 hydrate crystal of the compound represented by formula (I) are shown (measurement conditions: temperature 25°C, relative humidity 60%). In the table, position (Position) indicates 2θ (°), and intensity (Intensity) indicates intensity. Fig. 20 The peaks of the powder X-ray diffraction pattern of the anhydrate crystal of the compound represented by formula (I) are shown (measurement conditions: temperature 50°C, relative humidity 25%). In the table, position (Position) indicates 2θ (°), and intensity (Intensity) indicates intensity. Fig.21 Represents the peaks of the powder X-ray diffraction pattern (measurement conditions are temperature 25°C, relative humidity 35%) of the hydrate crystals of the compound represented by formula (I) (containing X molecules of water relative to 1 molecule of the compound represented by formula (I). However, 0<X<0.25). In the table, position (Position) represents 2θ (°), and intensity (Intensity) represents intensity. Fig. 22 The Raman spectrum of the hydrate crystal of the compound represented by formula (I) (containing X molecules of water per molecule of the compound represented by formula (I), but 0<X<0.25) is shown. The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.23 express Fig. 22 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.24 express Fig. 22 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.25 The figure shows the amorphous powder X-ray diffraction pattern of the compound represented by the formula (I) obtained in Example 1. The horizontal axis represents 2θ (°), and the vertical axis represents intensity (Count). Fig.26The water adsorption / desorption isotherm of the amorphous compound represented by formula (I) obtained in Example 1 is shown. The vertical axis represents the weight change (%) (Change In Mass), and the horizontal axis represents the relative humidity (%) (Target % P / P0, unit: %). The curve drawn with a diamond is the water adsorption isotherm, and the curve drawn with a square is the water desorption isotherm. Fig. 27 The Raman spectrum of the amorphous compound represented by formula (I) obtained in Example 1 is shown. The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.28 express Fig. 27 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.29 express Fig. 27 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.30 The peaks of the powder X-ray diffraction pattern of the crystal of the compound represented by formula (II) are shown. In the table, the position (Position) represents 2θ (°), and the intensity (Intensity) represents the intensity. Fig.31 The Raman spectrum of the crystal of the compound represented by formula (II) is shown. The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.32 express Fig.31 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.33 express Fig.31 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.34 The amorphous powder X-ray diffraction pattern of the compound represented by formula (II) is shown. The horizontal axis represents 2θ (°) and the vertical axis represents intensity (Count). Fig.35 The water adsorption / desorption isotherm of the amorphous compound represented by formula (II) is shown. The vertical axis represents the weight change (%) (Change In Mass), and the horizontal axis represents the relative humidity % (Target % P / P0). The curve drawn with a diamond is the water adsorption isotherm, and the curve drawn with a square is the water desorption isotherm. Fig.36 The Raman spectrum of the amorphous compound represented by formula (II) is shown. The horizontal axis represents the Raman shift (cm-1 ), the vertical axis represents the peak intensity. Fig.37 express Fig.36 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.38 express Fig.37 The horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the peak intensity. Fig.39 The powder X-ray diffraction pattern of the B-type crystal of the compound represented by formula (I) is shown. The horizontal axis represents 2θ (°) and the vertical axis represents intensity. Fig.40 The peaks of the powder X-ray diffraction pattern of the B-type crystal of the compound represented by formula (I) are shown. In the table, the position (Position) represents 2θ (°), and the intensity (Intensity) represents the intensity. DETAILED DESCRIPTION
[0013] Unless otherwise specified, the values in this specification and the scope of the patent application are approximate values. The value changes are caused by device calibration, device error, purity of the substance, crystal size, sample size, temperature, and other factors.
[0014] The meanings of the terms used in this specification are explained below. Unless otherwise specified, each term has the same meaning when used alone or in combination with other terms. The term "consisting of" means that only the constituent elements are present. The term "comprising" or "including" means that the constituent elements are not limited and that unrecited elements are not excluded. In addition, throughout this specification, unless otherwise specified, singular expressions should be understood to include the concept of plural forms. Therefore, singular articles (such as "a", "an", "the", etc. in English) should be understood to include the concept of plural forms unless otherwise specified. In addition, the terms used in this specification, unless otherwise mentioned, should be understood to be used in the sense commonly used in the above-mentioned fields. Therefore, unless otherwise defined, all technical terms and scientific and technological terms used in this specification have the same meaning as those commonly understood by technicians in the technical field to which the present invention belongs. In the event of a conflict, this specification (including definitions) shall take precedence.
[0015] The present invention relates to a crystal of a compound represented by formula (I) or (II). The crystal may be a single-phase crystal or a mixed crystal. The selection and control of solid form is particularly important for compounds that will become pharmaceuticals. Careful selection and control of solid form can reduce problems with the manufacture, formulation, or administration of the compound.
[0016] In addition, the term "crystal" as used in this specification refers to a solid whose constituent atoms, ions, molecules, etc. are regularly arranged in three dimensions, and is distinguished from an amorphous solid that does not have such a regular internal structure. The crystal of the present invention may be a single crystal, a twin crystal, a polycrystal, or the like. Furthermore, "crystals" may have "polymorphs" that have the same composition but different arrangements in the crystal, and all of these are called "crystal forms." Crystal morphology and degree of crystallinity can be determined by a number of techniques including, for example, powder X-ray diffraction, Raman spectroscopy, infrared absorption spectroscopy, water adsorption / desorption, differential scanning calorimetry, and solubility characteristics.
[0017] One aspect of the present invention is "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of not more than that of 0.25 hydrate". As used in this specification, "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than 0.25 equivalent to that of a hydrate" means crystals containing 0 to 0.25 molar equivalents of water molecules (crystallization water) relative to 1 molecule of the compound represented by formula (I). "Anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than 0.25 equivalent to that of a hydrate" are affected by the external environment (relative humidity and / or temperature). There may be cases where water molecules in the air are adsorbed and / or dehydrated, and the adsorption and dehydration are reversible. That is, "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than 0.25 equivalent to that of a hydrate" may be affected by the external humidity and / or temperature, and water molecules in the air may easily enter and exit the crystals in the crystal lattice as crystallization water.
[0018] "Crystallization water" as used in this specification refers to water present in the crystal lattice. "Adherent water" as used in this specification refers to water attached to the surface of the crystal, also known as "free water". It is known that crystallization water and attached water contribute differently to the stability and solubility of drugs.
[0019] When the "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals having a water content equal to or less than that of the 0.25 hydrate" are identified in the powder X-ray diffraction pattern (Cu Kα line), The diffraction angles (2θ) include characteristic peaks at 13.05°±0.25°, 18.35°±0.25°, 20.05°±0.35°, 20.45°±0.25° and 23.75°±0.25°. In the case of identifying more peaks, characteristic peaks are found at diffraction angles (2θ): 13.05°±0.25°, 15.55°±0.25°, 16.65°±0.25°, 17.00°±0.30°, 18.35°±0.25°, 19.35°±0.35°, 20.05°±0.35°, 20.45°±0.25°, 21.45°±0.25° and 23.75°±0.25°.
[0020] The "hydrate" used in the present specification refers to, for example, a compound represented by formula (I) or (II) in which an arbitrary number of water molecules are regularly arranged.
[0021] The "hydrate crystal" used in this specification refers to a crystal in which, for example, a compound represented by formula (I) or (II) and an arbitrary number of water molecules are regularly arranged. Water present in the crystal lattice of the hydrate crystal is referred to as "crystallization water". The hydrate crystal of the crystal of "the compound represented by formula (I)" of the present invention is preferably "a hydrate crystal of the compound represented by formula (I) having a water content of not more than the water content equivalent to 0.25 hydrate".
[0022] One aspect of the present invention is "a hydrate crystal of a compound represented by formula (I) having a water content of not more than the water content equivalent to 0.25 hydrate". “Hydrate crystals of the compound represented by formula (I) having a water content of less than or equal to that of 0.25 hydrate” means “0.25 hydrate crystals of the compound represented by formula (I)” and / or “hydrate crystals of the compound represented by formula (I) having a water content less than that of 0.25 hydrate”.
[0023] One aspect of the present invention is "0.25 hydrate crystal of the compound represented by formula (I)". "0.25 hydrate crystals of the compound represented by formula (I)" refers to crystals containing 0.25 molar equivalents of water molecules per 1 molecule of the compound represented by formula (I), that is, crystals in which 1 water molecule is regularly arranged per 4 molecules of the compound represented by formula (I). The theoretical content of water of crystallization of "0.25 hydrate crystals of the compound represented by formula (I)" is 0.86% by weight. However, in the analysis of the water content, there may be cases where the value obtained is higher than the theoretical content of water of crystallization due to the influence of the attached water and / or attached solvent attached to the surface of the crystal. For example, there may be cases where it is 0.86 to 1.5% by weight. In addition, part of the water of crystallization is scattered, and in the analysis of the water content, there may be cases where a value lower than the theoretical content of water of crystallization is obtained.
[0024] The 0.25 hydrate crystals were subjected to powder X-ray diffraction (CuKα line, ) is identified, There are characteristic peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 19.9°±0.2°, 20.5°±0.2° and 23.7°±0.2°. In the case of more peaks to be identified, There are characteristic peaks at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.5±0.2°, 18.4°±0.2°, 19.2°±0.2°, 19.9°±0.2°, 20.5°±0.2°, 21.5°±0.2°, 23.7°±0.2° and 24.2°±0.2°.
[0025] In addition, the 0.25 hydrate crystals were When performing single crystal diffraction experiments at 213K (-60°C), the crystallographic data have the following characteristics: Space group: P1 α=92.1°±0.5° β=105.3°±0.2° γ=92.3°±0.5°.
[0026] One aspect of the present invention is "a hydrate crystal of a compound represented by formula (I) having a water content less than that of a 0.25 hydrate". One aspect of the present invention is a "hydrate crystal of a compound represented by formula (I) (containing X molecules of water per molecule of the compound represented by formula (I), but 0<X<0.25)". As used in this specification, “hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate” and “hydrate crystals of the compound represented by formula (I) (containing X molecules of water molecules per molecule of the compound represented by formula (I), but 0<X<0.25)” have the same meaning. “Hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrates” and “Hydrate crystals of the compound represented by formula (I) (containing X molecules of water molecules relative to 1 molecule of the compound represented by formula (I), but 0<X<0.25)” refer to crystals containing less than 0.25 molar equivalents of water molecules relative to 1 molecule of the compound represented by formula (I). The theoretical content of crystal water of "hydrated crystals of a compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrates" and "hydrated crystals of a compound represented by formula (I) (containing X molecules of water molecules relative to 1 molecule of the compound represented by formula (I), but 0<X<0.25)" is less than 0.86% by weight. However, in the analysis of the water content, there may be cases where a value higher than the theoretical content of crystal water is obtained due to the influence of attached water and / or attached solvent attached to the surface of the crystal. In addition, part of the crystal water is scattered, and in the analysis of the water content, there may be cases where a value lower than the theoretical content of crystal water is obtained.
[0027] The hydrate crystals (hydrate crystals of the compound represented by formula (I) having a water content less than that of 0.25 hydrate) were subjected to a powder X-ray diffraction pattern (CuKα line, ), The diffraction angles (2θ) include characteristic peaks at 13.0°±0.2°, 18.4°±0.2°, 20.0°±0.2°, 20.4°±0.2° and 23.7°±0.2°. In the case of identifying more peaks, characteristic peaks are found at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.4±0.2°, 18.4°±0.2°, 19.3°±0.2°, 20.0°±0.2°, 20.4°±0.2°, 21.4°±0.2°, 23.7°±0.2° and 24.1±0.2°.
[0028] One aspect of the present invention is "anhydrous crystals of the compound represented by formula (I)". As used herein, "anhydrous" has the same meaning as "non-solvate", "non-solvate", "anhydrate" and "non-hydrate". The theoretical content of crystal water of the "anhydrous crystals of the compound represented by formula (I)" is 0% by weight. However, in the analysis of the water content, the content may be higher than the theoretical content of crystal water due to the influence of the attached water and / or attached solvent attached to the crystal surface.
[0029] The anhydrate crystals were subjected to powder X-ray diffraction (CuKα line, ), There are characteristic peaks at diffraction angles (2θ): 13.1°±0.2°, 18.3°±0.2°, 20.2°±0.2°, 20.5°±0.2° and 23.8°±0.2°. When more peaks are identified, characteristic peaks are found at diffraction angles (2θ): 13.1°±0.2°, 15.6°±0.2°, 16.7°±0.2°, 17.1±0.2°, 18.3°±0.2°, 19.5°±0.2°, 20.2°±0.2°, 20.5°±0.2°, 21.5°±0.2° and 23.8°±0.2°.
[0030] In addition, the anhydrate crystals were observed under CuKα radiation. When performing single crystal diffraction experiments at 213K (-60°C), The crystallographic data are characterized by: Space group: P21 α=90° β=105.3°±0.2° γ=90°.
[0031] The "crystal of the compound represented by formula (I)" may absorb water and become a hydrate, or may be dehydrated and become an anhydrate, depending on the change in relative humidity and / or temperature. In other words, it may be a crystal that can easily enter and exit the crystal lattice as water molecules in the air as crystal water depending on the change in external humidity and / or temperature.
[0032] “Anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than the water content equivalent to 0.25 hydrate” may be crystals in which water molecules in the air can easily enter and exit the crystal lattice as crystal water depending on changes in external relative humidity and / or temperature. That is, depending on external relative humidity and / or temperature, “anhydrate crystals of the compound represented by formula (I)” and “hydrate crystals of the compound represented by formula (I) having a water content of less than the water content equivalent to 0.25 hydrate” may undergo reversible transformation. Similarly, depending on external relative humidity and / or temperature, “anhydrate crystals of the compound represented by formula (I)”, “hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate” and “0.25 hydrate crystals of the compound represented by formula (I)” may undergo reversible transformation. For the above-mentioned crystals, even if the powder X-ray diffraction pattern slightly changes when the water content varies, as long as the characteristic peaks described in this specification are present, it can be interpreted as being substantially the same crystal. Since the powder X-ray diffraction pattern of the crystal as described above is affected by the environment (relative humidity and / or temperature) in which the powder X-ray diffraction experiment is performed, the powder X-ray diffraction experiment may be performed in a specific environment with controlled relative humidity and / or temperature.
[0033] One aspect of the present invention is a crystal represented by formula (I), which is placed on a powder X-ray diffraction apparatus at a temperature of 25° C. and a relative humidity of 60%, and then subjected to a powder X-ray diffraction experiment (CuKα line, )hour, There are characteristic peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 19.9°±0.2°, 20.5°±0.2° and 23.7°±0.2°. One aspect of the present invention is a crystal represented by formula (I), which is placed on a powder X-ray diffraction apparatus at a temperature of 25° C. and a relative humidity of 60%, and then subjected to a powder X-ray diffraction experiment (CuKα line, )hour, There are characteristic peaks at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.5±0.2°, 18.4°±0.2°, 19.2°±0.2°, 19.9°±0.2°, 20.5°±0.2°, 21.5°±0.2°, 23.7°±0.2° and 24.2°±0.2°. In addition, before the powder X-ray diffraction experiment, the crystal is left to stand under relative humidity and temperature control for, for example, 1.5 hours or more, more preferably 3 hours or more, and most preferably 20 hours or more.
[0034] One aspect of the present invention is a crystal represented by formula (I), which is placed on a powder X-ray diffraction apparatus at a temperature of 25° C. and a relative humidity of 35%, and then subjected to a powder X-ray diffraction experiment (CuKα line, )hour, The diffraction angles (2θ) include characteristic peaks at 13.0°±0.2°, 18.4°±0.2°, 20.0°±0.2°, 20.4°±0.2° and 23.7°±0.2°. One aspect of the present invention is a crystal represented by formula (I), which is placed on a powder X-ray diffraction apparatus at a temperature of 25° C. and a relative humidity of 35%, and then subjected to a powder X-ray diffraction experiment (CuKα line, )hour, There are characteristic peaks at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.4°±0.2°, 18.4°±0.2°, 19.3°±0.2°, 20.0°±0.2°, 20.4°±0.2°, 21.4°±0.2°, 23.7°±0.2° and 24.1±0.2°. In addition, before the powder X-ray diffraction experiment, the crystal is left to stand under relative humidity and temperature control for, for example, 1.5 hours or more, more preferably 3 hours or more, and most preferably 20 hours or more.
[0035] One aspect of the present invention is a crystal represented by formula (I), which is placed on a powder X-ray diffraction apparatus at a temperature of 50° C. and a relative humidity of 25%, and then subjected to a powder X-ray diffraction experiment (CuKα line, )hour, There are characteristic peaks at diffraction angles (2θ): 13.1°±0.2°, 18.3°±0.2°, 20.2°±0.2°, 20.5°±0.2° and 23.8°±0.2°. One aspect of the present invention is a crystal represented by formula (I), which is left to stand at 50° C. and 25% relative humidity on a powder X-ray diffraction device, and then subjected to a powder X-ray diffraction experiment (CuKα line) under the same environment. There are characteristic peaks at 13.1°±0.2°, 15.6°±0.2°, 16.7°±0.2°, 17.1±0.2°, 18.3°±0.2°, 19.5°±0.2°, 20.2°±0.2°, 20.5°±0.2°, 21.5°±0.2° and 23.8°±0.2°. In addition, before the powder X-ray diffraction experiment, the crystal is left to stand under relative humidity and temperature control for, for example, 1.5 hours or more, more preferably 3 hours or more, and most preferably 20 hours or more.
[0036] One aspect of the present invention is "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of not more than that of 0.25 hydrate" having a melting point of 236 to 237°C. One aspect of the present invention is "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than that of 0.25 hydrate" having a melting point of 236 to 237°C as measured by differential scanning calorimetry (DSC) or simultaneous thermogravimetric and differential thermal analysis (TG / DTA).
[0037] One aspect of the present invention is "a hydrate crystal of a compound represented by formula (I) having a water content Y (wt%) of 0.0<Y≦5.0 wt%". Preferably, it is "a hydrate crystal of a compound represented by formula (I) having a water content Y (wt%) of 0.0<Y≦3.0 wt%". More preferably, it is "a hydrate crystal of a compound represented by formula (I) having a water content Y (wt%) of 0.0<Y≦1.5 wt%".
[0038] One aspect of the present invention is that in the Raman spectrum, at 1448 cm -1 ±2cm -1 、1511cm -1 ±2cm -1 and 2885cm -1 ±2cm -1 "Anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of not more than that of 0.25 hydrate" having an absorption peak. One aspect of the present invention is that in the Raman spectrum, at 1448 cm -1 ±2cm -1 、1511cm -1 ±2cm -1 、1650cm -1 ±2cm -1 、2885cm -1 ±2cm -1 and 2947cm -1 ±2cm -1 "Anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of not more than that of 0.25 hydrate" having an absorption peak.
[0039] One aspect of the present invention is a crystal of a compound represented by formula (II). The crystal was subjected to powder X-ray diffraction (CuKα line, ), There are characteristic peaks at diffraction angles (2θ): 16.3°±0.2°, 18.4°±0.2°, 20.4°±0.2°, 22.8°±0.2° and 23.9°±0.2°. In the case of more peaks to be identified, There are characteristic peaks at diffraction angles (2θ): 15.1°±0.2°, 16.3°±0.2°, 18.4°±0.2°, 19.2°±0.2°, 20.4°±0.2°, 21.1°±0.2°, 22.0°±0.2°, 22.8°±0.2°, 23.3°±0.2° and 23.9°±0.2°.
[0040] One aspect of the present invention is a crystal of a compound represented by formula (II), which has a Raman spectrum at 577 cm -1 ±2cm -1 、612cm -1 ±2cm -1 、740cm -1 ±2cm -1 、1571cm -1 ±2cm -1 and 1718cm -1 ±2cm -1 Has an absorption peak.
[0041] One aspect of the present invention is an anhydrate crystal of the compound represented by formula (II).
[0042] In addition, the compound represented by formula (I) or (II) may take the form of a solvate crystal. In this case, the solvate refers to, for example, a compound represented by formula (I) or (II) in which an arbitrary number of solvent molecules are regularly arranged. Preferably, it is a hydrate crystal. Examples of solvent molecules other than water include acetonitrile, chlorobenzene, chloroform, cyclohexane, 1,2-dichloroethylene, dichloromethane, 1,2-dimethoxyethane, N,N-dimethylacetamide, N,N-dimethylformamide, 1,4-dimethoxyethane, Alkane, 2-ethoxyethanol, ethylene glycol, formamide, hexane, methanol, 2-methoxyethanol, methyl butyl ketone, methylcyclohexane, N-methylpyrrolidone, nitromethane, pyridine, cyclopentane, tetralin, toluene, 1,1,2-trichloroethylene, xylene, acetic acid, anisole, 1-butanol, 2-butanol, tert-butanol, n-butyl acetate, tert-butyl methyl ether, isopropylbenzene, dimethyl sulfoxide, ethyl acetate, diethyl ether, ethyl formate, formic acid, heptane, acetic acid Isobutyl ester, isopropyl acetate, methyl acetate, 3-methyl-1-butanol, methyl ethyl ketone, methyl isobutyl ketone, 2-methyl-1-propanol, pentane, 1-pentanol, 1-propanol, 2-propanol, propyl acetate, tetrahydrofuran, methanol, ethanol, acetone, 1,1-diethoxypropane, 1,1-dimethoxymethane, 2,2-dimethoxypropane, isooctane, isopropyl ether, methyl isopropyl ketone, methyltetrahydrofuran, petroleum ether, trichloroacetic acid and trifluoroacetic acid. Preferred examples include acetic acid, anisole, 1-butanol, 2-butanol, n-butyl acetate, tert-butyl methyl ether, isopropylbenzene, dimethyl sulfoxide, ethyl acetate, diethyl ether, ethyl formate, formic acid, heptane, isobutyl acetate, isopropyl acetate, methyl acetate, 3-methyl-1-butanol, methyl ethyl ketone, methyl isobutyl ketone, 2-methyl-1-propanol, pentane, 1-pentanol, 1-propanol, 2-propanol, propyl acetate, tetrahydrofuran, methanol, ethanol, acetone, 1,1-diethoxypropane, 1,1-dimethoxymethane, 2,2-dimethoxypropane, isooctane, isopropyl ether, methyl isopropyl ketone, methyltetrahydrofuran, petroleum ether, trichloroacetic acid, and trifluoroacetic acid. More preferably, there can be mentioned methanol, ethanol, acetone, 1,1-diethoxypropane, 1,1-dimethoxymethane, 2,2-dimethoxypropane, isooctane, isopropyl ether, methyl isopropyl ketone, methyltetrahydrofuran, petroleum ether, trichloroacetic acid, and trifluoroacetic acid.
[0043] The crystal of the present invention may be a deuterium-converted body. The crystal of the present invention may be composed of isotopes (e.g. 2 H. 3 H. 14 C. 35 S. 125 I, etc.) marking.
[0044] The radioactive labeled form of the compound represented by formula (I) or (II) can be prepared by methods well known in the art. For example, the tritium-labeled compound represented by formula (I) can be prepared by introducing tritium into the specific compound represented by formula (I) using a catalytic dehalogenation reaction of tritium. This method comprises reacting a halogen-substituted precursor of the compound represented by formula (I) with tritium gas in the presence of a suitable catalyst such as Pd / C and in the presence or absence of a base. Other suitable methods for preparing tritium-labeled compounds can be found in "Isotopes in the Physical and Biomedical Sciences, Vol. 1, Labeled Compounds (Part A), Chapter 6 (1987)". 14 C-labeled compounds can be prepared by using 14 C carbon raw materials and prepared.
[0045] Mode: The compound represented is a MGAT2 inhibitor described in Patent Document 1 (International Publication No. WO2019 / 013311) and Patent Document 2 (WO2019 / 013312). It is very useful as a therapeutic agent or preventive agent for diseases in which MGAT2 is involved. The compound represented by formula (I) or (II) can be prepared by the method described in Patent Documents 1 and 2, etc.
[0046] (X-ray powder diffraction (XRPD)) Powder X-ray diffraction (XRPD) is one of the most sensitive analytical methods for determining the crystal morphology and crystallinity of solids. When X-rays are irradiated on a crystal, they are reflected on the crystal lattice planes, interfere with each other, and display diffraction lines in an orderly manner corresponding to the periodicity of the structure. On the other hand, for amorphous solids, since there is usually no orderly repeating period in their structure, no diffraction phenomenon occurs, and a featureless broad XRPD pattern (also called a halo pattern) is displayed.
[0047] The characteristic diffraction peak used in this specification is a peak selected from the observed diffraction pattern. The characteristic diffraction peak is preferably about 10, more preferably about 5, selected from the diffraction pattern. In terms of distinguishing multiple crystals, peaks that are confirmed in the crystal but not confirmed in other crystals are preferred characteristic peaks for identifying the crystals, compared to the peak intensity. If it is such a characteristic peak, even one or two peaks can give the crystal characteristics. If the patterns obtained by comparative measurement are consistent with these characteristic peaks, it can be said that the powder X-ray diffraction patterns are substantially consistent.
[0048] Generally, since the diffraction angle (2θ) of powder X-ray diffraction may have an error within the range of ±0.2°, it should be understood that the value of the diffraction angle of powder X-ray diffraction also includes a value within the range of about ±0.2°. Therefore, not only crystals whose diffraction angles of the peaks of powder X-ray diffraction are completely consistent, but also crystals whose diffraction angles of the peaks are consistent with an error of about ±0.2° are included in the present invention.
[0049] The intensity of the peaks shown in the following figures is known to vary due to various factors, such as the effect of the preferred orientation of the crystals for the X-ray beam, the influence of coarse particles, the purity of the substance being analyzed, or the degree of crystallinity of the sample. In addition, the peak position can be shifted based on the change in the sample height. Furthermore, if different wavelengths are used for measurement, different shifts can be obtained according to the Bragg formula (nλ=2dsinθ), but other XRPD patterns obtained by using these other wavelengths are also included in the scope of the present invention.
[0050] The crystal form of the compound represented by formula (II) can be identified by the powder X-ray diffraction pattern and characteristic diffraction peaks. The crystal form of the compound represented by formula (II) can be distinguished from other crystal forms by the presence of characteristic diffraction peaks.
[0051] The crystals of the compound represented by formula (I) can be identified by the powder X-ray diffraction pattern and characteristic diffraction peaks. In addition, "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than or equal to a water content of 0.25 hydrates" are reversibly transformed between anhydrate crystals and hydrate crystals having a water content of less than or equal to a water content of 0.25 hydrates, depending on the external relative humidity and / or temperature, and water molecules in the air can easily enter and exit the crystal lattice as crystallization water. That is, "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than or equal to a water content of 0.25 hydrates" are reversibly transformed between anhydrate crystals, hydrate crystals having a water content of less than or equal to a water content of 0.25 hydrates, and 0.25 hydrate crystals, depending on the external relative humidity and / or temperature, and water molecules in the air can easily enter and exit the crystal lattice as crystallization water. Since this change is only the entry and exit of water molecules in the crystal lattice, "anhydrate crystals of the compound represented by formula (I) and hydrate crystals of the compound represented by formula (I) having a water amount of less than the water amount equivalent to 0.25 hydrate" show almost the same diffraction angle (2θ), but (A1) 0.25 hydrate crystals, (A2) anhydrate crystals, and hydrate crystals between (A1) and (A2) (containing X molecules of water molecules relative to 1 molecule of compound represented by formula (I). However, 0<X<0.25) also have characteristic diffraction angles (2θ).
[0052] By combining a powder X-ray diffraction apparatus with a device for controlling temperature and / or relative humidity, powder X-ray diffraction measurement can be performed at a specific temperature and / or relative humidity. In the case where anhydrous crystals are converted to hydrated crystals due to moisture absorption, in the case where hydrated crystals are converted to anhydrous crystals due to dehydration, in the case where anhydrous crystals and hydrated crystals undergo reversible transformation due to moisture absorption / dehydration, it is suitable for measurement at a specific temperature and / or relative humidity, and measurement with continuous changes in temperature and / or relative humidity. In these cases, the relative humidity and amount of crystal water that will cause the transformation can be estimated. The powder X-ray diffraction pattern of "anhydrate crystals of the compound represented by formula (I) and hydrate crystals of the compound represented by formula (I) having a water content of not more than the water content equivalent to 0.25 hydrate" is affected by the environment (relative humidity and / or temperature) in which the powder X-ray diffraction experiment is performed, so there are cases where the powder X-ray diffraction experiment is performed under a specific environment with controlled relative humidity and / or temperature. In addition, for the crystal, when it is desired to correctly identify the crystal form by powder X-ray diffraction, it is preferably measured under a specific relative humidity and / or temperature environment.
[0053] (XRD-DSC powder diffraction) The simultaneous measurement of powder X-ray diffraction and differential scanning calorimetry (XRD-DSC measurement) can simultaneously observe changes in crystal morphology (crystal structure) and thermal changes with respect to temperature and relative humidity. It is suitable for the determination of when anhydrous crystals are converted into hydrated crystals due to moisture absorption, when hydrated crystals are converted into anhydrous crystals due to dehydration, and when anhydrous crystals and hydrate crystals undergo reversible crystal conversion due to moisture absorption / dehydration.
[0054] (Single crystal structure analysis) It is one of the methods for identifying crystals. It can obtain the crystallographic parameters of the crystal, and further obtain the atomic coordinates (values indicating the spatial positional relationship of each atom) and the three-dimensional structural model. See Toshio Sakurai's "Guide to X-ray Structure Analysis" published by Shokabo (1983), Stout & Jensen's X-Ray Structure Determination: A Practical Guide, Macmillan Co., New York (1968), etc. Single crystal structure analysis is useful for identifying the structures of optical isomers, tautomers, geometric isomers, and solvates (hydrates). In addition, it is known that single crystal X-ray diffraction experiments can improve data quality by measuring at low temperatures. It is known that single crystal X-ray diffraction experiments of hydrates and / or solvates can improve data quality by coating the crystals with paraffin oil or the like before measuring.
[0055] (Raman spectroscopy) Raman spectroscopy shows the characteristics of vibration of molecules or composite systems. It originates from the inelastic collision between molecules and light particles containing light, that is, photons. The collision between molecules and photons brings about the exchange of energy, and as a result, the energy changes, and thus the wavelength of the photons changes. That is, since Raman spectra are spectral lines with extremely narrow wavelengths generated when photons are injected into the target molecules, lasers can be used as light sources. The wavelength of each Raman line is expressed as a wave number shift from the incident light, which is the difference between the Raman line and the reciprocal of the wavelength of the incident light. Raman spectroscopy is used to measure the vibration state of molecules, which is determined by their molecular structure. Usually, the absorption band in Raman spectroscopy (cm -1 ) Due to the possibility of ±2cm -1 Therefore, the above absorption peak values should be understood to include about ±2cm -1 Therefore, the present invention includes not only crystals whose Raman spectrum peaks are completely consistent with each other, but also crystals whose Raman spectrum peaks are within the range of about ±2 cm -1 Error and consistent crystal.
[0056] (Infrared absorption spectrometry (IR method)) Infrared absorption spectrometry is a method for measuring the degree of absorption of infrared rays when passing through a sample for each wave number. Infrared absorption spectra are usually represented by a graph with the horizontal axis set as wave number and the vertical axis set as transmittance or absorbance. In addition to reading the wave number and transmittance (or absorbance) of the absorption peak from the graph, values calculated by a data processing device can also be used. Infrared absorption spectra are determined by the chemical structure of the substance. Therefore, the absorption at various wave numbers can be measured to confirm or quantify the substance. The discrimination of polymorphism can be carried out by comparing the absorption bands of its polymorphic characteristic functional groups, that is, the functional groups mainly participating in the hydrogen bond in the crystal structure, such as C=O bond, OH bond and NH bond, and other characteristic functional groups, such as CX (halogen) bond, C=C bond and C≡C bond. It is selected from about 20 absorption peaks corresponding to the characteristic functional groups, more preferably about 10 absorption peaks, and optimally about 5 absorption peaks. Usually, the absorption spectrum of the sample is at a wave number of 4000cm -1 Up to 400cm -1 The absorption spectrum was measured under the same operating conditions as those used to confirm the resolution, wave number scale, and wave number accuracy of the device.
[0057] Usually, due to the absorption band (cm -1 ) may be within ±2cm -1 Therefore, it should be understood that the above absorption peak value also includes about ±2cm -1Therefore, the present invention includes not only crystals whose absorption band peaks measured by infrared absorption spectrum are completely consistent, but also crystals whose absorption band peaks are within about ±2 cm -1 Error and consistent crystal.
[0058] There are several methods for measuring infrared absorption spectra, such as potassium bromide tablet method, solution method, paste method, liquid film method, thin film method, gas sample measurement method, ATR method, diffuse reflectance method, etc. Among them, the ATR method (attenuated total reflection) is called the total reflection measurement method and is a type of reflection method. This method is to make the sample close to the surface of a prism made of a high refractive index material such as KRS-5, and to inject light into the prism at an angle above the critical angle, and to measure the light totally reflected at the boundary between the prism and the sample to obtain the absorption spectrum. One of the conditions that can be measured by the ATR method is that the refractive index of the prism is greater than that of the sample, so it is necessary to change the material of the prism according to the sample. In addition, as another condition, the prism and the sample must be in close contact. Therefore, it is suitable for the measurement of liquids, powders, plastics, soft rubbers, etc., and has the advantage that the sample can be measured without chemical or physical treatment. On the other hand, the diffuse reflectance method is a method in which potassium bromide tablets are not made in the measurement of powder samples, and the powder is directly measured. When light is irradiated onto a sample, light is reflected directly from the powder surface to the outside, and diffusely reflected light (scattered light) enters the sample and repeatedly penetrates and diffuses to the surface. In the diffuse reflectance method, the latter is used to obtain an absorption spectrum.
[0059] (solid 13 C-NMR (Nuclear Magnetic Resonance) solid 13 C-NMR has the following advantages: (i) the spectral number is consistent with the carbon number of the target compound, and (ii) the chemical shift range is 1 H-NMR has a wide spectrum, (iii) the signal is more sensitive than solid 1H-NMR, and (iv) there is no chemical shift even when additives are present. In addition, the chemical shift observed is expected to vary slightly depending on the specific spectrometer used and the analyst's sample modulation technique. 13 The error range of the C-NMR spectrum is about ±0.5 ppm.
[0060] (Differential Scanning Calorimetry (DSC)) DSC is one of the main measurement methods of thermal analysis and is a method of measuring thermal properties of a substance as an aggregate of atoms / molecules. DSC measures the temperature or time-dependent heat change of a pharmaceutical active ingredient, and plots the obtained data against temperature or time to obtain a differential scanning calorimetry curve. From the differential scanning calorimetry curve, information on the onset temperature (extrapolated melting point start temperature) when the pharmaceutical active ingredient melts, the maximum value of the endothermic peak curve accompanying the melting, and the enthalpy can be obtained. For DSC, it is known that the observed temperature can depend on the rate of temperature change and the sample modulation technique and the specific device used. Therefore, the "melting point" in DSC refers to the starting temperature (extrapolated melting point onset temperature) that is not easily affected by the sample modulation technique. The error range in the starting temperature (extrapolated melting point onset temperature) obtained from the differential scanning calorimetry curve is about ±2°C. In the determination of crystal identity, not only the melting point but also the overall pattern is important, which can vary slightly depending on the measurement conditions or the measurement machine.
[0061] (Thermogravimetric and differential thermal analysis (TG / DTA)) TG / DTA is one of the main measurement methods of thermal analysis, and is a method of measuring the weight and thermal properties of a substance as an aggregate of atoms / molecules. TG / DTA is a method for measuring the weight and heat changes of active pharmaceutical ingredients in relation to temperature or time. The TG (thermogravimetric) and DTA (differential thermal) curves are obtained by plotting the obtained data against temperature or time. From the TG / DTA curve, information on the weight and heat changes of the decomposition, dehydration, oxidation, reduction, sublimation, and evaporation of active pharmaceutical ingredients can be obtained. For TG / DTA, it is known that the observed temperature and weight changes can depend on the temperature change rate and the sample modulation technique and specific equipment used. Therefore, the "melting point" in TG / DTA refers to the starting temperature (extrapolated melting point start temperature) that is not easily affected by the sample modulation technique. In the determination of crystal identity, not only the melting point but also the overall pattern is important, which can vary slightly depending on the measurement conditions or measurement equipment.
[0062] (Water adsorption / desorption isotherm measurement (DVS)) The water adsorption / desorption isotherm measurement is a measurement method for measuring the adsorption and desorption behavior of water by measuring the weight change of a solid to be measured under various relative humidity conditions. In terms of the basic measurement method, the dry weight at 0% RH (relative humidity 0%) is used as the reference, and the relative humidity is increased by 5% or 10%. After the weight at each relative humidity stabilizes, the amount of adsorbed water can be calculated from the weight increase of the reference value. Similarly, the amount of water desorption can be measured by decreasing the relative humidity by 5% or 10% from 100% RH or 95% RH. By plotting the weight change at each relative humidity, an adsorption-desorption isotherm can be obtained. From this result, the adsorption and desorption phenomenon of attached water at each humidity can be examined. The adsorption and desorption of attached water and crystal water are affected by particle size, degree of crystallinity, crystal habit, etc., so the measurement results may vary slightly.
[0063] Differential scanning calorimetry (DSC), thermogravimetric and differential thermal analysis (TG / DTA), water adsorption / desorption isotherm analysis (DVS), Karl Fischer moisture analyzer, and gas chromatography are analytical methods for detecting attached water and / or attached solvent (residual solvent) on the "surface" of crystals. In this analysis, when measuring a sample having attached water and / or attached solvent on the surface of the crystal, there may be a case where the amount of water and / or solvent is higher than the theoretical content of crystal water in hydrate crystals and / or the theoretical content of crystal solvent in solvate crystals. In contrast, powder X-ray diffraction and single crystal structure analysis are methods for analyzing the "internal structure" of crystals. Regardless of whether there is water and / or solvent (residual solvent) attached to the "surface" of the crystal, characteristic peaks will be displayed at the same position. Raman spectroscopy and infrared absorption spectrometry (IR method) are also the same. Therefore, in powder X-ray diffraction, single crystal structure analysis, Raman spectroscopy, and infrared absorption spectrometry (IR method), even if there is a case where the amount of water and / or solvent is higher than the theoretical content in the crystal, as long as there are characteristic peaks recorded in the specification, it can be interpreted as substantially the same crystal. As described above, there are cases where a powder X-ray diffraction experiment or a single crystal structure analysis experiment is performed in a specific environment where the relative humidity and / or temperature are controlled, but there are cases where the controlled environment of the experiment is inconsistent with the results of the analysis method for detecting attached water and / or attached solvent. For example, the relative humidity controlled when performing the powder X-ray diffraction experiment is inconsistent with the relative humidity value of the water adsorption / desorption isotherm measurement method (DVS).
[0064] The pharmaceutical composition containing the crystal of the present invention is very useful as a therapeutic agent or a preventive agent for diseases in which MGAT2 is involved. Examples of diseases in which MGAT2 is involved include obesity, metabolic syndrome, hyperlipidemia, high lipidemia, hyperVLDLemia, hyperfatty acidemia, diabetes, and / or arteriosclerosis.
[0065] The crystal of the present invention can be administered to human patients by itself or as a pharmaceutical composition prepared by mixing the crystal with an appropriate carrier or excipient. The pharmaceutical formulation and administration technique can be a combination of formulations or techniques known to those skilled in the art, and can be appropriately selected and used.
[0066] The administration route of the crystal of the present invention or the pharmaceutical composition containing the same is not limited, and may include oral, rectal, transmucosal or intestinal administration, or intramuscular, subcutaneous, intraspinal, intrathecal, directly intraventricular, intravenous, intravitreal, intraperitoneal, intranasal, intraocular, injection. The preferred administration route is oral.
[0067] The pharmaceutical composition of the present invention can be manufactured by methods well known in the art, for example, by conventional mixing, dissolving, granulating, sugar-coating, powdering, emulsifying, encapsulating, including, and freeze-drying steps.
[0068] The crystals of the present invention or pharmaceutical compositions containing them can be administered by injection using an aqueous solution, preferably a physiologically suitable buffer such as Ringer's solution or physiological saline.
[0069] The crystal of the present invention or a pharmaceutical composition containing the same can be administered transmucosally using a penetrant appropriate to the barrier to be permeated. Such a penetrant can be one generally known in the art.
[0070] The crystal of the present invention or the pharmaceutical composition containing the same can be orally administered by combining with a pharmaceutically acceptable carrier well known in the art. The crystal of the present invention can be administered in the form of tablets, pills, buccal tablets, sugar-coated tablets, capsules, liquids, gels, syrups, or suspensions. The pharmaceutical composition for oral administration can be prepared by using a solid excipient, adding other appropriate supplements if necessary, pulverizing the obtained mixture, and treating the mixture of particles to obtain tablets or sugar-coated tablet cores.
[0071] For the crystals of the invention or their pharmaceutical compositions, the therapeutically effective amount can be estimated from the initial enzyme assay. Then, multiple dosages can be prescribed for use in animal models in a manner that achieves a circulating concentration range that includes the IC50 (i.e., the concentration of the crystals of the invention or their pharmaceutical compositions that achieves half-maximal inhibition of PK activity) determined by the enzyme assay. Then, using this information, the useful amount for humans can be more accurately determined.
[0072] The therapeutic effect of the crystal or its pharmaceutical composition of the present invention can be measured by standard pharmaceutical methods in purified enzymes or experimental animals. For example, it can be evaluated according to the biological test method described in Patent Document 1. The data obtained from these enzyme analyses and animal experiments can be used to prescribe the range of dosages for human use. The dosage can vary depending on the dosage form used and the dosage route used. Regarding the correct prescription dosage route and dosage, each physician can choose according to the patient's condition.
[0073] It is also an aspect of the present invention that the crystal or pharmaceutical composition of the present invention can be combined with other pharmaceutical agents for the treatment of diseases and disorders.
[0074] According to the present invention, an anhydrate crystal and a hydrate crystal of a compound represented by formula (I) and a crystal of a compound represented by formula (II) are provided. The crystal has at least any of the following characteristics. (1) It has good stability against heat, humidity, solvents, light, etc. and high storage stability. (2) After light irradiation, no significant coloration is shown. (3) Good solubility in water or organic solvents. (4) It dissolves quickly in water or organic solvents. (5) High purity. (6) The residual rate of organic solvent is low. (7) It has excellent operability in filtration, centrifugal separation, formulation, etc. (8) Smaller specific volume. (9) Not easily electrified. (10) It can be produced at a high yield under conditions with little environmental impact and can be produced in large quantities. (11) A pharmaceutical active ingredient useful as an oral preparation, injection, or the like, or a raw material for its production. (12) Since the pH can be controlled within a range suitable for intravenous injection without vascular pain, it is advantageous in controlling the amount of liquid or reducing the amount of excipients during preparation. (13)Good liquidity. (14) Compression degree (%) is low. In particular, the crystal of the present invention has high stability even in a wide humidity range (eg, 25 to 95% RH, etc.) or in a harsh environment (eg, high humidity), and has good solubility in water or organic solvents. Example
[0075] The present invention is described in more detail by the following examples, but the present invention is not limited thereto. Slight errors and deviations should be considered for numerical values (such as amounts, temperatures, etc.). Unless otherwise indicated, % are by weight of ingredients and % by weight of the total composition, and pressures are at or near atmospheric pressure.
[0076] (Measurement of powder X-ray diffraction pattern) Powder X-ray diffraction measurement was performed according to the powder X-ray diffraction measurement method described in the General Test Methods of the Japanese Pharmacopoeia. The measurement conditions are as follows. Measurement condition 1: Powder X-ray diffraction device: SmartLab manufactured by Rigaku Corporation Measurement method: Reflectometer Use wavelength: CuKα line Tube current: 200mA Tube voltage: 45kV Sample plate: Aluminum X-ray incident angle: 2.5° Sampling width: 0.02° Detector: HyPix-3000 (2D detection mode) Measurement condition 2: D-8Discover manufactured by Bruker (Operation method) Measurement method: Reflectometer Use wavelength: CuKα line Tube current: 40mA Tube voltage: 40kV Sample plate: Aluminum X-ray incident angle: 3° and 12°
[0077] (Measurement of powder X-ray diffraction pattern under temperature and relative humidity control) The temperature and relative humidity of the sample portion were controlled using an attachment attached to the X-ray diffraction device, and the powder X-ray diffraction measurement was performed in accordance with the powder X-ray diffraction measurement method described in the General Test Methods of the Japanese Pharmacopoeia. The measurement conditions are as follows. Measurement condition 3: (X-ray diffraction measurement) Powder X-ray diffraction apparatus: RINT2100Ultima+ manufactured by Rigaku Corporation Measurement method: Reflectometer Use wavelength: CuKα line Tube current: 40mA Tube voltage: 40kV Sample plate: Aluminum X-ray measurement range: 5°-35° Sampling width: 0.02° Scanning speed: 60° / min (Temperature and relative humidity control) Temperature controller: ThermoPlus manufactured by Rigaku Corporation Control temperature: 25℃ Humidity controller: HUM-1 manufactured by Rigaku Corporation Control humidity: relative humidity 60%
[0078] Measurement condition 4: The X-ray diffraction measurement under measurement condition 3 was performed by setting the following conditions using the controller described under measurement condition 3. Control temperature: 25℃ Control humidity: relative humidity 35%
[0079] Measurement condition 5: The X-ray diffraction measurement under measurement condition 3 was performed by setting the following conditions using the controller described under measurement condition 3. Control temperature: 50℃ Control humidity: relative humidity 25%
[0080] Measurement condition 6: The controller described in Measurement Condition 3 was used to set the following conditions and perform X-ray diffraction measurement under Measurement Condition 3. Controlled temperature: from room temperature to 80°C, at a rate of 5°C / min. (Temperature control was not performed)
[0081] (Determination and analysis method of single crystal structure analysis) The single crystal structure analysis of the crystal obtained in each example was performed. The measurement conditions and analysis method are as follows. (Device) XtaLAB P200 MM007 made by Rigaku Corporation (Measurement conditions) Measuring temperature: -60℃ Temperature controller: Rigaku Co., Ltd. sample injection low temperature device Use wavelength: CuKα line Software: CrysAlisPro 1.171.39.46e (Rigaku Oxford Diffraction, 2018) (Data Processing) Software: CrysAlisPro 1.171.39.46e (Science Oxford Diffraction, 2018) The data were corrected for Lorentz, polarization, and absorption. (Crystal structure analysis) Phase determination was performed using the direct method program ShelXT (Sheldrick, GM, 2015), and refinement was performed using ShelXL (Sheldrick, GM, 2015) using full-matrix least squares methods. Temperature factors for non-hydrogen atoms were all refined anisotropically. Hydrogen atoms were introduced by calculation using ShelXL's preset parameters and treated as riding atoms. Water molecules were excluded, and hydrogen atoms were refined using isotropic parameters. Figures 4 to 11The plots were constructed using PLATON (Spek, 1991) / ORTEP (Johnson, 1976) (30% PROBABILITY level).
[0082] (Raman spectroscopy measurement) The following shows the measurement conditions of the Raman spectra of the crystal and amorphous substance obtained in each example and the measurement conditions for performing the baseline correction. Measurement condition 1 Measurement method: Microscopic laser Raman spectroscopy Laser wavelength: 671nm Cumulative times: 1-10 times Exposure time: 0.5-10 seconds Measurement condition 2 Measurement method: Microscopic laser Raman spectroscopy Laser wavelength: 785nm Cumulative times: 1-10 times Exposure time: 1-10 seconds
[0083] (Differential Scanning Calorimetry (DSC)) The crystals obtained in each example were measured by DSC. The sample was weighed in an aluminum pan and simply sealed for measurement. The measurement conditions were as follows. In addition, the measurement by differential scanning calorimetry (DSC) had an error within the range of ±2°C. Device: TA Instrument Q2000 / TA Instrument Measuring temperature range: -10℃-250℃ Heating rate: 10℃ / min Gas environment: N2 50mL / min
[0084] (TG / DTA measurement) The crystals obtained in each example were weighed, placed in an aluminum pan, and opened for measurement. The measurement conditions were as follows. Device: Hitachi High-Technologies Corporation TG / DTASTA7200RV Measurement temperature range: room temperature - 300°C Heating rate: 10℃ / min
[0085] (Water adsorption / desorption isotherm measurement (DVS)) The crystals and amorphous substances obtained in each example were weighed in an aluminum pan and left to stand at 25°C and 0% relative humidity. The measurement was started after the compound was fully dried and the weight was stabilized, and the weight was recorded every 5% change from 0% to 95% relative humidity. Then, the weight was recorded every 5% change from 95% to 0% relative humidity. Device: DVS Advantage manufactured by Surface Measurement Systems Example 1
[0086] By the same method as that described in Example 14 of Patent Document 1, an amorphous compound represented by formula (I) was obtained. To the obtained amorphous compound represented by formula (I) (5 mg) was added ethanol (500 μL), and the mixture was stirred at 60° C. for 5 minutes. After being allowed to stand until the mixture returned to room temperature, the solvent was evaporated to dryness to obtain crystals. Example 2
[0087] The crystals of the compound represented by formula (I) obtained in Example 1 were placed on a powder X-ray diffraction apparatus at 25° C. and 60% relative humidity and then subjected to a powder X-ray diffraction experiment under measurement condition 3. As a result, in the powder X-ray diffraction pattern, peaks were observed at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.5±0.2°, 18.4°±0.2°, 19.2°±0.2°, 19.9°±0.2°, 20.5°±0.2°, 21.5°±0.2°, 23.7°±0.2°, and 24.2°±0.2°. In the above powder X-ray diffraction pattern, the peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 19.9°±0.2°, 20.5°±0.2° and 23.7°±0.2° are particularly characteristic as "0.25 hydrate crystals of the compound represented by formula (I)". Figure 1 represents the powder X-ray diffraction pattern, Fig.19 Represents the peak list of the powder X-ray diffraction pattern. Example 3
[0088] 5 mg of the crystal of the compound represented by formula (I) obtained in Example 1 was added to 1 mL of a 5% aqueous acetone solution and dissolved by heating at 60° C. Then, the solution was left to cool to room temperature and the solvent was evaporated to obtain a single crystal. The obtained single crystal was coated with paraffin oil and fixed to a MicroMount (manufactured by MiTeGen), then mounted in a measurement section of a diffraction device set to -60°C, instantaneously cooled, and a single crystal X-ray diffraction experiment was performed.
[0089] The analysis was performed by the method described in the above (Measurement and analysis method of single crystal structure analysis). In addition, the occupancy of oxygen (labeled as O21) in water molecules was analyzed to be 1, and hydrogen was not introduced into O21. The results of the single crystal structure analysis are shown below. R1 (I>2.00s(I)) was 0.0925, and the final difference Fourier analysis confirmed that there was no lack of electron density and no misplacement.
[0090] Table 1 shows the crystallographic data. [Table 1] Here, V refers to the unit cell volume, and Z refers to the number of molecules in the unit cell.
[0091] Tables 2 to 3 show the atomic fraction coordinates x, y, z (×10 4 ) and the equivalent isotropic temperature factor U(eq) (Equivalent Isotropic Displacement Parameters), ). Here, U(eq) is defined as the straight-line U ij One third of the tensor trajectory. [Table 2] atom x y z U(eq) atom x y z U(eq) S1 5703(2) 8533.1(18) 13106.5(16) 49.4(5) N5 8664(7) 5761(6) 13033(5) 41.4(16) S3 4347(2) 3670.4(18) -2891.9(16) 51.7(6) N9 6222(7) 2287(8) 2050(5) 55(2) S2 5313(3) 765(2) 6465(2) 68.6(8) C79 1381(7) 8159(6) 4420(5) 34.6(16) S4 4901(5) 5444(3) 3835(3) 103.0(16) C55 3346(8) 1995(6) 460(6) 38.0(17) F5 2465(7) 537(4) 2260(4) 60.7(16) F4 7423(11) 367(7) -1198(5) 106(3) F3 7630(7) 634(5) 1830(5) 71.2(18) C5 7719(8) 6668(7) 10411(6) 40.1(18) O14 4405(6) 1983(5) 422(4) 46.1(15) C42 7476(8) 2090(8) 1062(6) 47(2) F1 7432(6) 5485(4) 7738(4) 62.4(16) O12 3142(8) 3382(8) -3403(6) 75(2) F8 2484(7) 6134(5) 8754(4) 69.6(18) C33 8782(8) 3175(6) 5849(5) 39.5(18) O19 5205(5) 7162(5) 7258(4) 45.8(14) O17 5773(8) 5439(8) 3341(7) 81(3) F6 1809(7) 1878(6) 48%(4) 71.9(19) C4 7808(8) 6568(6) 11315(5) 36.3(17) O9 4901(5) 2149(6) 2901(4) 50.7(16) C51 2326(8) 1778(6) -315(5) 35.4(17) O4 5650(6) 6821(6) 9677(4) 53.7(17) C64 1534(9) 2934(7) 2768(6) 46(2) O13 3558(8) 3443(5) -994(5) 58.7(19) C14 10680(8) 6006(6) 12919(6) 39.8(18) N17 1935(6) 7946(5) 5312(5) 37.6(15) C9 8855(8) 6425(6) 10313(6) 38.0(17) N10 8012(7) 3344(6) 6328(5) 46.7(17) C83 1652(8) 8580(7) 3075(6) 41.7(19) N7 8214(7) 2944(6) 4922(5) 39.9(15) C18 8761(8) 7865(8) 7464(6) 45(2) O18 4053(8) 5832(5) 5597(5) 56.8(18) C82 423(9) 8614(7) 2710(6) 43.2(19) N11 3059(7) 1932(5) -1692(4) 39.3(15) C10 9463(8) 6000(6) 12581(6) 39.4(18) N16 3859(6) 7417(5) 5167(5) 37.4(15) C54 1796(7) 2255(6) 1286(5) 37.2(17) N1 7001(7) 6745(5) 11811(5) 41.3(16) C49 3715(9) 2802(7) -1496(6) 47(2) N8 8884(7) 3051(6) 4315(5) 43.8(17) C20 7879(9) 6254(8) 7357(6) 47(2) N19 4011(7) 7555(6) 8152(5) 41.6(16) C52 1191(8) 1472(7) -222(5) 40.1(18) O3 6488(8) 8243(5) 11259(5) 61.0(19) O7 6448(9) 1229(9) 6927(6) 84(3) O11 5277(8) 3598(6) -3333(6) 65(2) C13 11119(9) 5785(7) 13801(6) 43.4(19) O15 1237(10) 3826(6) 2448(5) 73(2) C41 7437(10) 2511(8) 243(6) 52(2) O5 9243(7) 8718(5) 7887(5) 59.7(19) O10 7354(13) 3456(6) 127(6) 97(4) N20 2132(7) 8384(6) 3932(5) 40.4(16) C74 3212(7) 7623(7) 6586(5) 36.0(17) N6 6224(7) 2417(6) 50%(5) 43.1(17) C87 3033(9) 8522(10) 9960(7) 59(3) O1 6914(7) 8486(8) 13609(6) 73(2) C50 2226(7) 1673(6) -1226(5) 34.3(16) F7 2221(8) 7061(9) 11627(5) 107(4) C53 954(8) 1457(7) 671(6) 42.2(19) O20 3402(8) 9437(6) 9930(5) 62.4(19) C34 8507(9) 3537(7) 7211(6) 47(2) O8 5805(8) 832(6) 4460(6) 67(2) C59 -1134(9) 781(7) -3765(6) 47(2) F2 8238(7) 6821(8) 5215(4) 92(3) C72 4305(8) 6491(6) 5180(6) 41.0(18) N2 of 36(6) 6257(5) 11684(5) 37.1(14) C86 1802(10) 1967(9) 4024(6) 54(3) N15 3040(6) 2152(6) 1229(4) 37.8(15) C3 6351(9) 7568(7) 11718(6) 46(2) N4 7054(6) 7004(6) 8897(5) 40.9(16) C35 9718(10) 3608(7) 7611(6) 48(2) O2 4771(9) 8396(6) 13553(7) 77(3) C68 2100(10) 1305(7) 2709(6) 47(2) N14 1303(7) 825(5) -3005(5) 41.3(16) C88 2867(8) 7795(8) 9240(6) 44(2) N12 1085(6) 1306(5) -1608(4) 37.8(15) C7 8296(8) 7188(7) 8864(6) 40.5(19) N18 1322(6) 0 of 8(6) 5953(5) 41.0(16) C69 1802(8) 2161(7) 2265(6) 40.8(18) C78 4237(7) 7425(7) 7330(5) 37.4(17) C29 5938(8) 2302(7) 2848(6) 44(2) N3 9578(7) 6165(6) 11062(5) 42.4(16) C73 3088(8) 7657(7) 5681(5) 38.9(18) O6 4393(9) 722(8) 6951(7) 79(3) C56 543(8) 1035(6) -2522(5) 37.9(17) N13 442(7) 1174(6) -987(5) 41.3(16) C80 143(8) 8152(7) 4116(6) 39.8(18)
[0092] [Table 3]
[0093] Next, Table 4 shows the atomic coordinates x, y, z (×10 4 ) and isotropic temperature factor U(eq)(Isotropic Displacement Parameters, ). [Table 4]
[0094] Figure 4 represents the structure in the asymmetric unit of the crystal structure. Figures 5 to 8 Four molecular structure diagrams of the compound represented by formula (I) are shown respectively. The Flack parameter is 0.039(8), such as Figures 4 to 8 , the present compound contains a stereostructure and is confirmed to be a compound represented by formula (I). In addition, the numbers of non-hydrogen atoms in Tables 2 and 3 correspond to Figures 4 to 8 The number recorded in .
[0095] Since this crystal structure contained four molecules of the compound represented by the formula (I) and one water molecule in an asymmetric unit, it was identified as "0.25 hydrate crystal of the compound represented by the formula (I)".
[0096] The powder X-ray diffraction pattern was calculated from the crystal structure using Mercury (The Cambridge Crystallographic Data Centr, Ver. 4.0.0). Confirmed that the powder X-ray diffraction pattern of Example 2 ( Figure 1 ) are substantially consistent. It is thus inferred that Example 2 is a 0.25 hydrate crystal. Although a slight difference was observed between the two, since the measurement temperature of Example 2 was 25°C and the measurement temperature of Example 3 was -60°C, it is presumed that this is caused by the expansion and contraction of the crystal lattice due to the difference in measurement temperature. Example 4
[0097] Fig.12 The crystals of the compound represented by formula (I) obtained in Example 1 were weighed in an aluminum pan and subjected to differential scanning calorimetry (DSC) results. An endothermic peak with an onset temperature of about 237°C was shown. In addition, a small endothermic peak was seen at an onset temperature of about 34°C, so it is believed that some changes such as dehydration occurred. Based on the results of Example 6, it was determined that the endothermic peak at about 34°C was caused by dehydration. In addition, differential scanning calorimetry was performed on "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of not more than that of 0.25 hydrate" which were stored under different conditions or subjected to pulverization. All of them showed an endothermic peak with an onset temperature of about 237°C. Example 5
[0098] Fig.13 The results of thermogravimetric and differential thermal analysis (TG / DTA) of the crystals of the compound represented by the formula (I) obtained in Example 1 are shown. An endothermic peak with an onset temperature of about 236°C is shown. In addition, a weight loss rate of 0.8% was confirmed between the start of the measurement and about 100°C. This weight loss rate is converted as the water molecules (crystal water) in the "hydrate crystals of the compound represented by formula (I)", which is equivalent to about 0.23 hydrate. The crystals are thus identified as "hydrate crystals with a water content less than the water content equivalent to 0.25 hydrates". From the weight loss rate, it is highly likely that the crystals are "hydrate crystals with a water content less than the water content equivalent to 0.25 hydrates", but since the weight loss was confirmed from the start of the measurement, it cannot be determined whether it is a 0.25 hydrate crystal or a "hydrate crystal with a water content less than the water content equivalent to 0.25 hydrates". In addition, it was confirmed that the crystal water (including the attached water when present) was dehydrated to form anhydrous crystals from the start of the measurement to about 100°C. Therefore, the melting point of the "anhydrous crystals of the compound represented by formula (I)" was identified to be about 236 (TG / DTA results) to 237 (DSC results)°C. The results of Example 5 show that the "anhydrate crystals of the compound represented by formula (I) and / or the hydrate crystals of the compound represented by formula (I) having a water content of less than or equal to that of 0.25 hydrates" which were stored under different conditions or subjected to pulverization in Example 4 above all showed an endothermic peak with a starting temperature of about 237° C. After the "hydrate crystals having a water content of less than or equal to that of 0.25 hydrates" were converted into "anhydrate crystals of the compound represented by formula (I), it was determined that the melting point of the anhydrate was shown. Example 6
[0099] Fig.14 Table 5 shows the results of the water adsorption / desorption isotherm measurement (DVS) of the crystals of the compound represented by formula (I) obtained in Example 1. The difference in moisture content between 0% RH (relative humidity 0%) and 95% RH (relative humidity 95%) is about 1.4%. This moisture content is greater than the moisture content of the crystal water contained in the 0.25 hydrate crystals of the compound represented by formula (I) (theoretical value is 0.86 weight %), but it is judged to be affected by the attached water attached to the crystal surface. Therefore, the relative humidity value of the water adsorption / desorption isotherm measurement (DVS) is not necessarily consistent with the relative humidity controlled when performing the powder X-ray diffraction experiment. In addition, since no rapid change depending on humidity was observed in the adsorption-desorption isotherm, no clear crystal phase transition could be confirmed. Therefore, it is estimated that there was no significant crystal structure change due to adsorption-desorption caused by the change in relative humidity. [Table 5] Relative humidity (%) Water adsorption capacity (%) Water desorption amount (%) 0.0 0.000 0.063 5.0 0.064 0.153 10.0 0.115 0.230 15.0 0.174 0.316 20.0 0.234 0.395 25.0 0.321 0.509 30.0 0.449 0.638 35.0 0.549 0.740 40.0 0.639 0.830 45.0 0.719 0.917 50.0 0.798 0.989 55.0 0.867 1.052 60.0 0.925 1.113 65.0 1.003 1.179 70.0 1.070 1.237 75.0 1.150 1.288 80.0 1.196 1.314 85.0 1.266 1.369 90.0 1.350 1.407 95.0 1.426 1.426
[0100] Based on the results of Example 3 (analysis of the single crystal structure and powder X-ray diffraction pattern simulated from the crystal structure), Example 5 (simultaneous thermogravimetric and differential thermal analysis (TG / DTA)), and Example 6 (water adsorption / desorption isotherm measurement (DVS)), the crystals obtained in Example 2 were identified as "0.25 hydrate crystals of the compound represented by formula (I)". Example 7
[0101] The crystals of the compound represented by formula (I) obtained in Example 1 were left to stand at 50° C. and 25% relative humidity on a powder X-ray diffraction apparatus, and then subjected to a powder X-ray diffraction experiment under measurement condition 5. As a result, in the powder X-ray diffraction pattern, peaks were observed at diffraction angles (2θ): 13.1°±0.2°, 15.6°±0.2°, 16.7°±0.2°, 17.1±0.2°, 18.3°±0.2°, 19.5°±0.2°, 20.2°±0.2°, 20.5°±0.2°, 21.5°±0.2°, and 23.8°±0.2°. In the above powder X-ray diffraction pattern, peaks at diffraction angles (2θ): 13.1°±0.2°, 18.3°±0.2°, 20.2°±0.2°, 20.5°±0.2° and 23.8°±0.2° are particularly characteristic as “anhydrate crystals of the compound represented by formula (I)”. Figure 3 represents the powder X-ray diffraction pattern, Fig. 20 Represents the peak list of the powder X-ray diffraction pattern.
[0102] In the differential scanning calorimetry (DSC) of Example 4, the endothermic peak before the melting point has a starting temperature of about 34°C, and in the thermogravimetric and differential thermal simultaneous measurement (TG / DTA) of Example 5, the weight reduction ends at about 50°C. Therefore, under the sample standing conditions and measurement conditions (temperature 50°C, relative humidity 25%) of Example 7, it can be inferred that the water molecules of the hydrate crystals are dehydrated and become anhydrous crystals. That is, the powder X-ray diffraction pattern ( Figure 3 ) is judged to be a powder X-ray diffraction pattern of "anhydrate crystals of the compound represented by formula (I)". Example 8
[0103] The hydrate crystal (single crystal) of the compound represented by formula (I) was fixed on a MicroMount (manufactured by MiTeGen). At this time, no oil coating was performed, and a very small amount of paraffin oil was used on the contact part. Then, it was installed in the measuring part of the diffraction device set to 25°C, and nitrogen was blown at 25°C for 30 minutes. After that, the setting of the sample blowing low temperature device was lowered to -60°C at one go, and a single crystal X-ray diffraction experiment was carried out at -60°C.
[0104] The results of the single crystal structure analysis are shown below. R1 (I>2.00s(I)) is 0.0765, and the final differential Fourier analysis confirmed that there was no lack of electron density and no misplacement. Table 6 shows the crystallographic data. [Table 6] Here, V refers to the unit cell volume, and Z refers to the number of molecules in the unit cell.
[0105] Table 7 shows the atomic fraction coordinates x, y, z (×10 4 ) and the equivalent isotropic temperature factor U(eq) (Equivalent Isotropic Displacement Parameters), ). Here, U(eq) is defined as the straight-line U ij One third of the tensor trajectory. [Table 7] atom x y z U(eq) atom x y z U(eq) S1 5635.0(17) 6479.9(14) 7985.7(12) 52.0(4) C8 9096(5) 4248(5) 4400(4) 41.3(14) S2 5342(2) 3111(2) -1015.9(16) 71.4(6) C35 -382(6) 6237(5) -1860(4) 41.8(14) O9 5197(4) 5027(4) 2234(3) 42.5(10) C10 9510(6) 3809(5) 7608(4) 37.9(13) F1 7421(5) 3331(3) 2731(3) 61.8(12) C20 7826(6) 4097(6) 2321(4) 44.4(14) O4 5703(4) 4703(5) 4693(3) 50.3(12) C3 6409(6) 5497(6) 6868(4) 43.3(14) N7 1912(4) 5774(4) 244(3) 34.6(10) C21 7766(8) 3984(7) 1425(5) 58.3(19) N2 8988(4) 4066(4) 6697(3) 36.5(11) C26 4345(6) 4371(5) 91(4) 41.2(13) N9 3937(4) 5279(4) 3115(3) 38.4(11) C29 4191(5) 5229(5) 2300(4) 35.2(12) N5 8756(5) 3585(4) 8083(4) 43.1(12) C22 8158(7) 4806(7) 1027(4) 52.3(17) N4 7058(4) 4879(4) 3881(3) 38.6(11) C12 11182(6) 3599(5) 8846(4) 45.3(15) F2 8104(5) 4734(5) 134(3) 81.7(17) O10 3151(10) 6786(14) 5015(7) 158(7) N6 3867(5) 5300(4) 117(3) 39.4(11) C14 9218(7) 3377(6) 8956(5) 48.4(16) O3 6595(5) 6172(4) 6200(4) 59.4(14) C30 2876(6) 5726(6) 3292(4) 47.5(17) O5 9115(6) 6574(5) 2772(4) 70.5(17) C37 1559(6) 6363(5) -2046(4) 42.6(14) O8 4207(5) 3673(4) 551(4) 59.9(14) C13 10443(7) 3396(5) 9373(4) 47.2(15) N1 7053(5) 4623(5) 6817(4) 42.3(12) C11 10737(6) 3808(5) 7943(4) 41.0(14) N8 1283(4) 5873(5) 872(3) 41.1(12) C31 1754(6) 5552(7) 2518(4) 49.5(18) N3 9616(5) 3964(5) 6%3(3) 41.0(12) C23 8603(6) 5640(7) 1459(5) 50.6(17) O1 6806(6) 6354(6) 8560(4) 79.0(18) C38 -170(7) 6708(7) -3394(5) 60(2) N10 2%8(5) 6166(4) -1191(3) 39.3(11) C2 5447(6) 5535(6) 7146(5) 52.0(17) F4 2472(6) 3649(6) 3517(6) 105(2) O6 6267(6) 2692(6) -295(5) 81(2) O2 4652(6) 6364(5) 8375(5) 76.5(19) C16 8669(8) 6100(6) 4132(5) 54.3(18) C6 6755(5) 4728(5) 4647(4) 37.7(13) C46 2649(13) 5390(30) 5717(8) 185(15) C33 1348(6) 5983(5) -672(4) 37.1(12) C43 2530(8) 4207(13) 4221(9) 95(5) C27 3079(5) 5490(5) 625(4) 34.7(12) C15 10887(9) 3225(7) 10381(5) 65(2) C5 7759(5) 4508(5) 5418(4) 34.9(12) C42 2735(7) 5218(11) 4164(5) 79(4) C34 120(6) 6003(5) -966(4) 39.4(13) C25 4987(9) 4296(7) -651(7) 70(2) C32 2054(5) 5649(5) 1636(4) 38.7(13) C39 3078(9) 6866(8) 3432(6) 78(3) C7 8275(5) 5033(5) 3815(4) 34.4(12) F3 2417(8) 3904(18) 6491(6) 313(14) C18 8661(6) 5732(5) 2375(4) 42.8(14) C1 5495(10) 7599(8) 7451(7) 76(3) O7 5655(6) 3295(6) -1820(5) 76.0(19) C41 2867(9) 5850(20) 4938(6) 133(8) C36 344(6) 6448(5) -2424(4) 43.0(14) C45 2484(15) 4490(40) 5737(16) 280(30) C28 3177(5) 5425(5) 1540(4) 34.5(12) C24 4160(10) 2348(9) -1183(9) 93(4) C19 8268(5) 4932(5) 2825(4) 34.3(12) C17 9571(12) 6501(11) 3789(8) 91(3) C9 8861(5) 4242(5) 5303(4) 35.6(12) C44 2427(9) 3740(20) 4989(11) 177(12) C4 7865(5) 4402(5) 6326(4) 35.2(12) C40 3775(12) 7094(11) 4373(9) 117(6)
[0106] Next, Table 8 shows the atomic coordinates x, y, z (×10 4 ) and isotropic temperature factor U(eq)(Isotropic Displacement Parameters, ). [Table 8] atom x y z U(eq) atom x y z U(eq) H9 4454.69 5021.35 3571.84 46 H16A 7976.39 6542.59 3961.99 65 H4 6491.69 4886.75 3384.83 46 H16B 8944.13 6098.94 4789.81 65 H6 4063.33 5783.66 -193.9 47 H46 2632.76 5783.19 6218.02 222 H1 6952.77 4203.34 7221.61 51 H15A 10218.88 3081.98 10624.44 97 H34 -352.84 5863.9 -573.97 47 H15B 11291.67 3821.46 10665.51 97 H8A 8939.21 3584.86 4123.35 50 H15C 11432.25 2663.65 10496.62 97 H8B 9928.28 4418.98 4456.04 50 H25A 5730.57 4671.55 -448.69 84 H35 -1211.66 6253.15 -2086.87 50 H25B 4500.38 4646.84 -1177.81 84 H21 7482.18 3396.12 1105.07 70 H39A 3504.86 7119.03 3009.94 93 H12 12007.42 3598 9100.46 54 H39B 2309.02 7206.73 3307.08 93 H14 8698.08 3211.68 9306.46 58 H1A 5449.84 8128.69 7870.25 114 H37 2058.78 6453.94 -2427.8 51 H1B 4777.97 7599.22 6959.41 114 H11 11240.49 3942.63 7571.98 49 H1C 6176.93 7709.57 7215.52 114 H31A 1436.27 4882.32 2570.08 59 H24A 3465.74 2686.86 -1549.49 140 H31B 1146.29 6044.7 2552.7 59 H24B 4024.34 2171.53 -608.11 140 H23 8874.03 6159.72 1153.62 61 H24C 4307.71 1745.19 -1486.77 140 H38A -931.61 6378.44 -3614.32 90 H17A 10273.12 6069.55 3950.27 110 H38B 364.51 6485.52 -3741.15 90 H17B 9794.63 7166.91 4044.49 110 H38C -275.84 7426.86 -3455.56 90 H44 2331.92 3048.38 5043.03 213 H2A 5406.41 4882.57 7427.46 62 H40A 4541.08 6748.91 4499.32 140 H2B 4686.96 5644.09 6700.91 62 H40B 3928.98 7815.74 4432.67 140
[0107] Fig. 9 represents the structure in the asymmetric unit of the crystal structure. Figure 10 to Figure 11 Two molecular structure diagrams of the compound represented by formula (I) are shown respectively. The Flack parameter is 0.021(7), such as Figures 9 to 11 , the present compound contains a stereostructure and is confirmed to be a compound represented by formula (I). In addition, the numbers of non-hydrogen atoms in Table 7 correspond to Figures 9 to 11 The number recorded in .
[0108] Since the crystal structure has two molecules of the compound represented by formula (I) in the asymmetric unit and no other solvent or the like is present, it was identified as "anhydrate crystals of the compound represented by formula (I)".
[0109] The powder X-ray diffraction pattern was calculated from the crystal structure using Mercury (The Cambridge Crystallographic Data Centr, Ver. 4.0.0). Confirmed that the powder X-ray diffraction pattern of Example 7 ( Figure 3 ) are substantially consistent. Thus, Example 7 was identified as a powder X-ray diffraction pattern of anhydrous crystals. This is consistent with the point that it can be inferred to be an anhydrous substance based on the measurement conditions of Example 7 (temperature 50°C, relative humidity 25%), the results of differential scanning calorimetry (DSC) of Example 4, and the simultaneous thermogravimetric and differential thermal measurement (TG / DTA) of Example 5. In addition, although there is a slight difference between the powder X-ray diffraction pattern calculated from the crystal structure and the powder X-ray diffraction pattern of Example 7, the measurement temperature of Example 7 is 50°C, and the measurement temperature of Example 8 is -60°C, which is a large difference. Therefore, it is speculated that it is caused by the expansion and contraction of the crystal lattice due to the different measurement temperatures.
[0110] In addition, although the lattice constant of the "0.25 hydrate crystal of the compound represented by formula (I)" obtained in Example 3 and the lattice constant of the "anhydrate crystal of the compound represented by formula (I)" obtained in Example 8 are different in space group, the difference in a-axis is about The difference of the b axis is about The difference of c axis is about The difference in α is about 2.1°, the difference in β is about 0.02°, and the difference in γ is about 2.3°, which are very similar. Furthermore, the crystal structures of the two are also very similar. The points at which the amide part of the dihydropyridone of the compound molecule represented by formula (I) forms intermolecular hydrogen bonds with the amide part of the dihydropyridone of the adjacent compound molecule represented by formula (I) are also the same. It can be inferred from this that the 0.25 hydrate crystal and the anhydrate crystal are structures in which water reversibly enters and exits while roughly maintaining the crystal structure. In medicines, polymorphs such as hydrates and anhydrates are generally known to have greatly different lattice constants and crystal structures than those described above. The 0.25 hydrate crystals and anhydrate crystals of the compound represented by formula (I) are considered to be the same crystal form rather than being considered as ordinary polymorphs, with slight changes caused by the reversible inflow and outflow of water. The same is true for "hydrate crystals with a water content less than that of the 0.25 hydrate" which is an intermediate state between the two.
[0111] In addition to single crystal structure analysis, powder X-ray diffraction patterns of Example 2 ( Figure 1 ) and Example 7 ( Figure 3 ) are very similar, and the characteristic peaks are also roughly the same. Strictly speaking, slight differences are confirmed at the diffraction angles (2θ): 16.0° to 17.8°, 19.5° to 21.0°, and 23.5 to 24.2°. This slight difference can be inferred to be due to the presence or absence of water molecules. Example 9
[0112] After the powder X-ray diffraction experiment of Example 2, the sample environment on the powder X-ray diffraction device was changed to a temperature of 25° C. and a relative humidity of 35%, and the sample was left to stand, and the powder X-ray diffraction experiment was carried out under measurement condition 4. As a result, in the powder X-ray diffraction pattern, peaks were observed at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.4±0.2°, 18.4°±0.2°, 19.3°±0.2°, 20.0°±0.2°, 20.4°±0.2°, 21.4°±0.2°, 23.7°±0.2° and 24.1±0.2°. In the above-mentioned powder X-ray diffraction pattern, the peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 20.0°±0.2°, 20.4°±0.2° and 23.7°±0.2° are particularly characteristic as "hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate". Figure 2 represents the powder X-ray diffraction pattern, Fig.21 Represents the peak list of the powder X-ray diffraction pattern.
[0113] The powder X-ray diffraction pattern obtained in Example 9 ( Figure 2 ) and the powder X-ray diffraction pattern of the "0.25 hydrate crystal of the compound represented by formula (I)" obtained in Example 2 ( Figure 1 ) are very similar, and the characteristic peaks are also roughly the same. On the other hand, slight differences are confirmed in the diffraction angles (2θ): 16.0° to 17.8°, 19.5° to 21.0°, and 23.5 to 24.2°. Example 2 and Example 9 are powder X-ray diffraction experiments of exactly the same sample (same crystal), but the powder X-ray diffraction pattern and diffraction angle (2θ) are very similar, but slight differences are confirmed, depending on the environment (relative humidity and / or temperature) in which the powder X-ray diffraction experiment is performed. In other words, it is clear that the powder X-ray diffraction pattern and diffraction angle (2θ) of the "0.25 hydrate crystal of the compound represented by formula (I)" vary depending on the environment (relative humidity and / or temperature) in which the powder X-ray diffraction experiment is performed.
[0114] In addition, the powder X-ray diffraction pattern obtained in Example 9 ( Figure 2 ) and the powder X-ray diffraction pattern of the “anhydrous crystals of the compound represented by formula (I)” obtained in Example 7 ( Figure 3 ) are also very similar, and the characteristic peaks are also roughly the same. On the other hand, slight differences are confirmed in the diffraction angles (2θ): 16.0° to 17.8°, 19.5° to 21.0°, and 23.5 to 24.2°. That is, although the powder X-ray diffraction pattern obtained in Example 9 is very similar to the powder X-ray diffraction pattern of "0.25 hydrate crystals of the compound represented by formula (I)" and the powder X-ray diffraction pattern of "anhydrous crystals of the compound represented by formula (I)", slight differences are confirmed in the diffraction angles (2θ): 16.0° to 17.8°, 19.5° to 21.0°, and 23.5 to 24.2°. Since the powder X-ray diffraction patterns of Examples 2, 7 and 9 are very similar, and the crystal structures of the 0.25 hydrate crystals and anhydrate crystals obtained in Examples 3 and 8 are very similar, the "crystals of the compound represented by formula (I) under an environment of 25°C and 35% relative humidity" of Example 9 are similar to the crystal structures of the 0.25 hydrate crystals and anhydrate crystals, and are considered to be a crystal structure intermediate between the two.
[0115] Based on the water adsorption / desorption isotherm measurement (DVS) of Example 6 above, the powder X-ray diffraction pattern obtained in Example 9 was estimated to be a powder X-ray diffraction pattern of "hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate". In addition, the water adsorption / desorption isotherm of Example 6 is a gentle curve, and does not show a sharp change in specific relative humidity, so it is estimated that there is no significant change in the crystal structure due to the adsorption and desorption of crystal water. This result is consistent with the very similar points of the powder X-ray diffraction patterns of Examples 2, 7 and 9 and the very similar points of the crystal structures of Examples 3 and 8.
[0116] Therefore, the results of Examples 2, 7 and 9 show that "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content less than that of 0.25 hydrate" vary in the powder X-ray diffraction pattern and diffraction angle (2θ) depending on the environment (relative humidity and / or temperature) in which the powder X-ray diffraction experiment is performed. Therefore, the slight differences in the three powder X-ray diffraction patterns obtained in Examples 2, 7 and 9 are the differences in the crystal forms of "anhydrate crystals of the compound represented by formula (I)", "hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate", and "0.25 hydrate crystals of the compound represented by formula (I)". This difference is believed to be caused by the content of water of crystallization. Example 9B
[0117] A powder X-ray diffraction experiment was performed under measurement conditions 6 on the crystals of the compound represented by formula (I) obtained in Example 1 above. As a result, it was confirmed from the powder X-ray diffraction pattern that the sample (crystals) transformed from "0.25 hydrate crystals of the compound represented by formula (I)" to "hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate", and continuously transformed from "hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate" to "anhydrate crystals of the compound represented by formula (I)".
[0118] It is clear from the results of Examples 2, 7, 9 and 9B that for "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content less than that of 0.25 hydrate", when the powder X-ray diffraction experiment is carried out in the atmosphere without controlling to a specific temperature and / or relative humidity, it will be affected by the temperature and relative humidity (weather, climate, etc.) during the measurement, and the powder X-ray diffraction pattern will have slight differences. Example 9C
[0119] On a certain day, a powder X-ray diffraction experiment was conducted on the crystals of the compound represented by formula (I) obtained in Example 1 under the measurement condition 3 (without using a temperature controller and a humidity controller) in the atmosphere without controlling the temperature and relative humidity. The results were confirmed to be consistent with the results of Example 9. In this measurement, it was determined that the crystals were "hydrated crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate". On another day, a powder X-ray diffraction experiment was performed on the crystals of the compound represented by formula (I) obtained in Example 1 under the measurement condition 3 (without using a temperature controller and a humidity controller) in the atmosphere without controlling the temperature and relative humidity. The results were confirmed to be consistent with the results of Example 2. In this measurement, it was determined to be "0.25 hydrate crystals of the compound represented by formula (I)". Example 10
[0120] From the results of Examples 2, 7, 9 and 9B (powder X-ray diffraction experiment), Examples 3 and 8 (single crystal structure analysis), Examples 4 and 5 (thermal analysis) and Example 6 (water adsorption / desorption isotherm measurement (DVS)), it is more natural to consider that "anhydrate crystals of the compound represented by formula (I)", "hydrate crystals of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate" and "0.25 hydrate crystals of the compound represented by formula (I)" are the same crystal form rather than being considered as three different crystal forms, and that it is more natural to consider that there are slight changes caused by the reversible inflow and outflow of water. Here, in the specific "anhydrate crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of less than or equal to that of 0.25 hydrate" of the present invention, the diffraction angle (2θ) and variation of the powder X-ray diffraction pattern to be used as a basis are calculated as follows.
[0121] The diffraction angles (2θ) observed in the respective powder X-ray diffraction patterns of Examples 2, 7, and 9 were extracted, and the values thereof were tabulated with a measurement error of ±0.2°. Table 9 shows the results. [Table 9] Next, for the values showing approximately the same diffraction angle in Table 9, the minimum value (the minimum value of A, D, and G) and the maximum value (the minimum value of C, F, and I) considering the measurement error are extracted. The results are shown in J and K of Table 10. Furthermore, the average value and the variation of the minimum value J and the maximum value K are calculated and shown in L and M of Table 10. [Table 10] From these results, it can be said that "anhydrous crystals of the compound represented by formula (I) and / or hydrate crystals of the compound represented by formula (I) having a water content of not more than that of 0.25 hydrate" in the powder X-ray diffraction pattern, The diffraction angles (2θ) include characteristic peaks at 13.05°±0.25°, 18.35°±0.25°, 20.05°±0.35°, 20.45°±0.25° and 23.75°±0.25°. When identifying more peaks, It can be said that there are characteristic peaks at diffraction angles (2θ): 13.05°±0.25°, 15.55°±0.25°, 16.65°±0.25°, 17.00°±0.30°, 18.35°±0.25°, 19.35°±0.35°, 20.05°±0.35°, 20.45°±0.25°, 21.45°±0.25° and 23.75°±0.25°. Embodiment 11
[0122] Figure 22 to Figure 24 The results of the Raman spectrum of the crystal of the compound represented by the formula (I) obtained in the above Example 1 are shown (measurement condition 1). In addition, the absorption peaks are shown below. [Table 11] <![CDATA[Raman peak cm -1 > <![CDATA[Raman peak cm -1 > <![CDATA[Raman peak cm -1 > <![CDATA[Raman peak Cm -1 > 425 692 1026 1413 456 728 1071 1448 4% 754 1088 1485 521 774 1112 1511 541 819 1162 1609 559 848 1194 1650 580 887 1215 1720 602 902 1227 2885 622 917 1266 2928 644 939 1320 2947 655 965 1364 2999 671 994 1387 3078 From the results of Examples 9 and 6, it is presumed that the result is "hydrate crystals of the compound represented by formula (I) having a water content smaller than the water content equivalent to 0.25 hydrate".
[0123] In one embodiment, "hydrate crystals of the compound represented by formula (I) having a water content less than that of 0.25 hydrate" at 1448 cm -1 ±2cm -1 、1511cm -1 ±2cm -1 、1650cm -1 ±2cm -1 、2885cm -1 ±2cm -1 and 2947cm -1 ±2cm -1 Has a main absorption peak. In one embodiment, the "hydrate crystal of the compound represented by formula (I) having a water content less than the water content equivalent to 0.25 hydrate" has a hydrate selected from 1448 cm -1 ±2cm -1 、1511cm -1 ±2cm -1 、1650cm -1 ±2cm -1 、2885cm -1 ±2cm -1 and 2947cm -1 ±2cm -1 One or more absorption peaks of a group consisting of absorption peaks.
[0124] The anhydrate crystals and 0.25 hydrate crystals of the compound represented by formula (I) were also subjected to Raman spectrum measurement in the same manner under the conditions maintaining the respective crystal forms, and it was confirmed that they had the same absorption peaks. Example 12
[0125] 1000 μL of methyl isobutyl ketone (MIBK) was added to 10 mg of the crystal of the compound represented by formula (I) obtained in Example 1, heated to 60°C, shaken, and allowed to stand at room temperature. Then, the solvent was removed by a centrifugal evaporator to obtain type B crystal of the compound represented by formula (I). A powder X-ray diffraction experiment was performed on the B-type crystal. Fig.39 represents the powder X-ray diffraction pattern, Fig.40 A list showing the peak positions and intensities. The powder X-ray diffraction pattern of type B crystal is different from any of the following: A powder X-ray diffraction pattern having peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 20.0°±0.2°, 20.4°±0.2° and 23.7°±0.2°, A powder X-ray diffraction pattern having peaks at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.4±0.2°, 18.4°±0.2°, 19.3°±0.2°, 20.0°±0.2°, 20.4°±0.2°, 21.4°±0.2°, 23.7°±0.2° and 24.1±0.2°, A powder X-ray diffraction pattern having peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 19.9°±0.2°, 20.5°±0.2° and 23.7°±0.2°, A powder X-ray diffraction pattern having peaks at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.5±0.2°, 18.4°±0.2°, 19.2°±0.2°, 19.9°±0.2°, 20.5°±0.2°, 21.5°±0.2°, 23.7°±0.2° and 24.2°±0.2°, A powder X-ray diffraction pattern having peaks at diffraction angles (2θ): 13.1°±0.2°, 18.3°±0.2°, 20.2°±0.2°, 20.5°±0.2° and 23.8°±0.2°; and A powder X-ray diffraction pattern having peaks at diffraction angles (2θ): 13.1°±0.2°, 15.6°±0.2°, 16.7°±0.2°, 17.1±0.2°, 18.3°±0.2°, 19.5°±0.2°, 20.2°±0.2°, 20.5°±0.2°, 21.5°±0.2° and 23.8°±0.2°.
[0126] The B-type crystal was subjected to simultaneous thermogravimetric and differential thermal analysis (TG / DTA). The results showed an endothermic peak with a starting temperature of about 159 to 161°C and an endothermic peak with a starting temperature of about 236°C, and an exothermic peak was shown between the two endothermic peaks. In addition, a weight reduction rate of about 2.0 to 6.5% was confirmed at about 170°C after the measurement started. In addition, the weight reduction rate was different each time it was measured, and it was believed that the reason was that the weight began to decrease after the measurement started, so it was affected by the external environment (relative humidity and / or temperature) before the measurement. The melting point of the type B crystal was confirmed to be about 159 to 161° C. from the results of simultaneous thermogravimetric and differential thermal analysis (TG / DTA). The type B crystal was presumed to transform into anhydrous crystals of the compound represented by formula (I) after melting.
[0127] Therefore, from the results of the powder X-ray diffraction experiment and the simultaneous measurement of thermogravimetric and differential thermal analysis (TG / DTA), it was determined that type B crystals and "anhydrate crystals of the compound represented by formula (I) or hydrate crystals of the compound represented by formula (I) having a water content less than that of 0.25 hydrate" were different crystal forms. In addition, since the melting point of type B crystals is lower than the melting point of "anhydrate crystals of the compound represented by formula (I) or hydrate crystals of the compound represented by formula (I) having a water content less than that of 0.25 hydrate" (strictly speaking, anhydrate crystals of the compound represented by formula (I)), it is judged to be a quasi-stable crystal. Example 13
[0128] A powder X-ray diffraction experiment was performed under measurement condition 1 on the amorphous compound represented by formula (I) obtained in Example 1. Fig.25 The powder X-ray diffraction pattern was shown. No characteristic peak was observed, but a halo pattern was confirmed. Embodiment 14
[0129] Fig.26 Table 12 shows the results of the measurement of the water adsorption / desorption isotherms of the amorphous compound represented by the formula (I) obtained in Example 1 above. [Table 12] Relative humidity (%) Water adsorption (%) Water desorption amount (%) 0.0 0.002 -0.433 5.0 0.676 0.606 10.0 1.020 1.196 15.0 1.312 1.674 20.0 1.574 2.131 25.0 1.807 2.495 30.0 2.015 2.831 35.0 2.213 3.157 40.0 2.414 3.423 45.0 2.589 3.699 50.0 2.780 3.913 55.0 2.976 4.135 60.0 3.185 4.411 65.0 3.384 4.683 70.0 3.623 5.151 75.0 3.914 5.420 80.0 4.320 5.865 85.0 4.850 6.219 90.0 5.604 6.599 95.0 6.974 6.974
[0130] The difference in moisture content between 0%RH (0% relative humidity) and 95%RH (95% relative humidity) is as high as about 7.0%. Generally, solids with large changes in moisture content due to relative humidity will have a large change in drug content per weight unit depending on the humidity measured, so they are judged to be unsuitable as technical drugs. Embodiment 15
[0131] Figure 27 to Figure 29 The results of Raman spectrum of the amorphous compound represented by formula (I) are shown (measurement condition 1). In addition, the absorption peaks are shown below. [Table 13] Example 16
[0132] By the same method as that described in Example 12 of Patent Document 1, an amorphous compound represented by formula (II) was obtained. Acetone (200 μL) was added to the obtained amorphous compound represented by formula (II) (5 mg), and the mixture was stirred at room temperature for 5 days with a magnetic stirrer. The solvent was removed by filtration to obtain crystals. Embodiment 17
[0133] A powder X-ray diffraction experiment was performed under measurement condition 2 on the crystals of the compound represented by formula (II) obtained in Example 16 above. As a result, in the powder X-ray diffraction pattern, peaks were observed at diffraction angles (2θ): 15.1°±0.2°, 16.3°±0.2°, 18.4°±0.2°, 19.2°±0.2°, 20.4°±0.2°, 21.1°±0.2°, 22.0°±0.2°, 22.8°±0.2°, 23.3°±0.2°, and 23.9°±0.2°. In the powder X-ray diffraction pattern, peaks at diffraction angles (2θ): 16.3°±0.2°, 18.4°±0.2°, 20.4°±0.2°, 22.8°±0.2°, and 23.9°±0.2° are particularly characteristic of the crystals of the compound represented by formula (II). Fig.15 and Fig.30 The powder X-ray diffraction pattern is shown. Embodiment 18
[0134] About 1 mg of the crystal of the compound represented by formula (II) obtained in Example 16 was weighed in an aluminum pan. Fig.16 The results of DSC analysis are shown. The onset temperature was about 181°C. Embodiment 19
[0135] Fig.17The TG / DTA analysis results of the crystals of the compound represented by the formula (II) obtained in Example 16 above are shown. Embodiment 20
[0136] Fig.18 Table 14 shows the results of water adsorption / desorption isotherm measurement of the crystals of the compound represented by formula (II) obtained in Example 16. The difference in water content between 0% RH (relative humidity 0%) and 95% RH (relative humidity 95%) was about 0.4%, confirming that the crystals had no hygroscopicity problem. [Table 14] Relative humidity (%) Water adsorption (%) Water desorption amount (%) 0.0 0.0000 0.0690 5.0 0.0149 0.1029 10.0 0.0250 0.1252 15.0 0.0352 0.1435 20.0 0.0494 0.1610 25.0 0.0623 0.1773 30.0 0.0758 0.1922 35.0 0.0893 0.2077 40.0 0.1042 0.2206 45.0 0.1204 0.2348 50.0 0.1387 0.2497 55.0 0.1563 0.2659 60.0 0.1746 0.2822 65.0 0.2016 0.3038 70.0 0.2334 0.3289 75.0 0.2619 0.3464 80.0 0.2937 0.3627 85.0 0.3268 0.3782 90.0 0.3695 0.4013 95.0 0.4243 0.4243 Embodiment 21
[0137] Figure 31 to Figure 33 The results of Raman spectrum of the crystal of the compound represented by formula (II) are shown (measurement condition 2). The absorption peaks are shown below. [Table 15] <![CDATA[Raman peak cm -1 > <![CDATA[Raman peak cm -1 > <![CDATA[Raman peak cm -1 > <![CDATA[Raman peak Cm -1 > 447 768 1058 1410 470 788 1083 1433 489 805 1118 1483 531 852 1150 1531 577 882 1220 1571 591 908 1246 1596 612 927 1270 1614 671 955 1299 1652 728 998 1323 1695 740 1028 1390 1718
[0138] In one embodiment, the crystal of the compound represented by formula (II) is at 577 cm -1 ±2cm -1 、612cm -1 ±2cm -1 、740cm -1 ±2cm -1 、1571cm -1 ±2cm -1 and 1718cm -1 ±2cm -1 Has a main absorption peak. In one embodiment, the crystal of the compound represented by formula (II) has a -1 ±2cm -1 、612cm -1 ±2cm -1 、740cm -1 ±2cm -1 、1571cm -1 ±2cm -1 and 1718cm -1 ±2cm -1 One or more absorption peaks of a group consisting of absorption peaks. Embodiment 22
[0139] A powder X-ray diffraction experiment was performed under measurement condition 1 on the amorphous compound represented by formula (II) obtained in Example 16. Fig.34The X-ray diffraction pattern of the powder is shown. No characteristic peaks were observed, but a halo pattern was confirmed. Embodiment 23
[0140] Fig.35 Table 16 shows the results of the water adsorption / desorption isotherm measurement of the amorphous compound represented by formula (II) obtained in Example 16. The difference in water content between 0% RH (relative humidity 0%) and 95% RH (relative humidity 95%) is about 2.6%. [Table 16] Relative humidity (%) Water adsorption (%) Water desorption amount (%) 0.0 0.001 .0.004 5.0 0.242 0.453 10.0 0.353 0.715 15.0 0.457 0.916 20.0 0.556 1.067 25.0 0.651 1.194 30.0 0.741 1.311 35.0 0.831 1.412 40.0 0.922 1.510 45.0 1.003 1.60 1 50.0 1.096 1.688 55.0 1.186 1.776 60.0 1.285 1.870 65.0 1.382 1.964 70.0 1.498 2.062 75.0 1.612 2.166 80.0 1.744 2.278 85.0 1.915 2.398 90.0 2.168 2.522 95.0 2.597 2.597 Embodiment 24
[0141] Figure 36 to Figure 38 The results of the Raman spectrum of the amorphous compound represented by formula (II) are shown (measurement condition 2). In addition, the absorption peaks are shown below. [Table 17]
[0142] Test Example 1 Solid stability test The solid stability of the crystals of the compound represented by formula (I) obtained in Example 1 and the crystals of the compound represented by formula (II) obtained in Example 16 was evaluated for chemical stability under temperature, temperature and humidity conditions and light irradiation. The proportion (%) of the generated similar substances and the change in appearance were evaluated by HPLC. (Storage stability test) Accurately weigh about 10 mg of crystals in a 2 mL glass container with a polyethylene stopper. After sealing the glass container, store it at 40°C or 60°C for 2 weeks, 1 month, 2 months, 3 months or 6 months. The sample stored at 40°C is called a 40°C sealed storage product, and the sample stored at 60°C is called a 60°C sealed storage product. In the unsealed state of the glass container, store it at 40°C at a relative humidity of 75±5% or a relative humidity of 89±5% for 2 weeks, 1 month, 2 months, 3 months or 6 months, or store it in the presence of silica gel at 40°C for 1 month, 2 months, 3 months or 6 months. The samples stored at 40℃ and 75±5% relative humidity or 89±5% relative humidity are called 40℃ and 75% relative humidity (also expressed as 40±2℃ / 75±5%RH) or 40℃ and 89% relative humidity (also expressed as 40±2℃ / 89%RH) stored samples, and the samples stored in the presence of silica gel at 40℃ are called 40℃ and silica gel stored samples. In addition, the sealed stored samples at -40℃ are used as standard samples. (Photostability Test) A light stability test was conducted on the crystals of the compound represented by formula (I) obtained in Example 1. About 10 mg of the crystals were weighed accurately in a glass cell and made into a thin and uniform state. The crystals were irradiated with D65 light at a cumulative illuminance of 1,216,000 lx·hr at 25°C. This sample was called a light-irradiated product. Here, the case where there is no change in appearance is represented by (-), and the case where a slight change in appearance is seen is represented by (±). In addition, a sample stored under the same conditions and shielded from light with aluminum foil was used as a standard, and the stability (content of similar substances) was measured by an absolute calibration curve method using the HPLC method under the following conditions. (Analogous mass determination method) The amount of similar substances was determined by the area percentage method using the HPLC method under the following conditions: HPLC condition 1 was used for the crystals and amorphous of the compound represented by formula (I) obtained in Example 1, and HPLC condition 2 was used for the crystals of the compound represented by formula (II) obtained in Example 16. (HPLC condition 1) Detector: UV absorbance photometer (measurement wavelength 260nm) Column: YMC-Triart C18 ExRS, S-1.9μm, 3.0×100mm Column temperature: Constant temperature around 40°C Mobile phase A: 0.1% formic acid in water Mobile phase B: acetonitrile Flow rate: about 0.6mL / min Injection volume: 3μL Sample cooler temperature: about 6°C · Mobile phase delivery: The mixing ratio of mobile phase A and mobile phase B was changed as shown in Table 18 to control the concentration gradient. [Table 18] Time (minutes) A(%) B(%) 0.5 90 10 19 40 60 21 10 90 23 10 90 23.01 90 10 29.5 90 10 (HPLC condition 2) Column: Cortecs (2.7μm 3.0x100mm) Column temperature: 40°C UV detection wavelength: 254nm Mobile phase: [A] 0.1% trifluoroacetic acid aqueous solution, [B] acetonitrile were prepared into a gradient as shown in Table 19. Flow rate: 0.6mL / min [Table 19]
[0143] As a result, the crystals of the compound represented by formula (I) obtained in Example 1 and the crystals of the compound represented by formula (II) obtained in Example 16 were confirmed to be crystals excellent in solid stability under any conditions. The following table describes the amount (%) of total similar substances under representative measurement conditions. [Table 20] [Table 21]
[0144] Test Example 2 The crystals and amorphous forms of the compound represented by formula (I) obtained in Example 1 were sealed and stored at 40°C and 89% relative humidity for 3 months (40°C 89% RH 3M), and a solid stability test was performed to evaluate the quality of the analogs. (Preparation of sample solution) The sample solution was prepared in the following manner. The crystal or amorphous compound represented by the formula (I) obtained in Example 1 was dissolved in an acetonitrile aqueous solution (acetonitrile:water=1:1) to prepare a sample solution at a concentration of 500 μg / mL. (Analogous mass determination method) According to HPLC Condition 1 described in Test Example 1, the purity and the amount of similar substances were measured by the area percentage method.
[0145] (result) The following table shows the results of the crystal and amorphous of the compound represented by formula (I) obtained in Example 1. In addition, the impurities detected at a retention time (RT) of 17.527 minutes show an increase in amount relative to the standard product. The amorphous compound represented by the formula (I) obtained in Example 1 had a significant increase in impurities detected at a retention time (RT) of 17.527 minutes, but the crystal significantly suppressed the increase in impurities. [Table 22]
[0146] Test Example 3 (Powder solubility test) The solubility of the crystal of the present invention was evaluated when JP-1 solution, JP-2 solution, and JP-2 solution supplemented with taurocholic acid (TCA / JP2) were used as the measurement medium. The dissolved concentration (μg / mL) was evaluated by HPLC.
[0147] Weigh about 1 mg of the crystal of the present invention in a 4 mL glass container, and add 2 mL of JP-2 solution (1000 mL of water added to 1.70 g of potassium dihydrogen phosphate and 1.775 g of anhydrous disodium hydrogen phosphate) to each container. Seal with a polyethylene plug with a Teflon / polysilicone liner, shake at 37°C for 1 hour, filter, add 400 μL of methanol to 800 μL of the filtrate, and dilute 1.5 times. Confirm the presence of bubbles and precipitates, and quantify the compound of the crystal of the present invention using HPLC by the absolute calibration curve method to calculate the solubility. In addition, regarding I-236, I-275, and II-168 described in Patent Documents 1 and 2, the solubility of each compound crystal is also shown in the following table. (result) [Table 23] Regarding the crystal of the present invention, it is confirmed that the solubility is high. Usually, the compound becomes crystalline from amorphous, and the solubility decreases. The crystal of the present invention is compared with the crystals of the embodiment compounds I-236, I-275 and II-168 described in patent documents 1 and 2, and it is confirmed that the solubility of the crystal of the present invention is good.
[0148] Test Example 4 (Solubility test under DMSO addition conditions) Solubility was determined under 1% DMSO addition conditions. 2 μL of the compound solution was added to 198 μL of JP-1 solution and JP-2 solution, respectively. After shaking at room temperature for more than 1 hour, the mixture was filtered by suction. The filtrate was diluted 10 or 100 times with methanol / water = 1 / 1 (V / V) or acetonitrile / methanol / water = 1 / 1 / 2 (V / V / V), and the concentration in the filtrate was determined by absolute calibration curve method using LC / MS / MS or solid phase extraction (SPE) / MS. The composition of JP-1 liquid is as follows. Water was added to 2.0 g of sodium chloride and 7.0 mL of hydrochloric acid to make a volume of 1000 mL. The composition of JP-2 liquid is as follows. To 1 volume of a solution prepared by dissolving 3.40 g of potassium dihydrogen phosphate and 3.55 g of anhydrous disodium hydrogen phosphate in water to make 1000 mL, 1 volume of water was added.
[0149] The above-described test was performed on the compound of the present invention and compounds I-236, I-275 and II-168 described in Patent Documents 1 and 2. (result) The solubility under the condition of DMSO addition was 50 μmol / L in all cases, showing a good result.
[0150] Test Example 5 (Residual Solvent) The crystals and amorphous forms of the compound represented by formula (I) obtained in Example 1 are 1 Evaluate residual solvents by H-NMR or gas chromatography.
[0151] NMR measurement was performed on the amorphous compound represented by the formula (I) obtained in Example 1. As a result, 3.66% by weight of hexane was detected.
[0152] (Residual solvent content based on ICH code Q3C) Hexane is a solvent (Class 2) whose residual amount in drugs should be regulated. Therefore, the residual amount of hexane in drug raw materials must be adjusted to below the specified value. The following table shows Class 2 solvents based on ICH code Q3C. [Table 24] Since the amorphous compound represented by formula (I) obtained in Example 1 exceeded the concentration limit of hexane, it was found that the amorphous compound represented by formula (I) obtained in Example 1 was not suitable as a pharmaceutical raw material.
[0153] The crystals of the compound represented by formula (I) obtained in Example 1 were subjected to gas chromatography. As a result, no residual solvent was found in an amount detectable by NMR. It was found that the crystals of the compound represented by formula (I) obtained in Example 1 are excellent as a pharmaceutical raw material.
[0154] The preparation examples shown below are for illustrative purposes only and are not intended to limit the scope of the invention in any way. The compounds of the present invention can be administered as a pharmaceutical composition by any conventional route, especially enteral, such as oral, for example, in the form of tablets or capsules, or non-oral, for example, in the form of injection solutions or suspensions, topically, for example, in the form of emulsions, gels, ointments or creams, or in the form of nasal or suppositories. Together with at least one pharmaceutically acceptable carrier or diluent, the pharmaceutical composition of the compounds of the present invention in the form of free form or pharmaceutically acceptable salts can be manufactured by conventional methods by mixing, granulation or coating. For example, for oral compositions, tablets, granules, and capsules containing excipients, disintegrants, binders, lubricants, etc. and active ingredients can be prepared. In addition, for injection compositions, solutions or suspensions can be prepared, which can be sterilized, and preservatives, stabilizers, buffering agents, etc. can also be contained. Industrial Applicability
[0155] The crystal of the present invention is useful as a pharmaceutical raw material. In addition, a pharmaceutical composition containing the crystal of the present invention is very useful as a therapeutic agent or a preventive agent for a disease in which MGAT2 is involved.
Claims
1. Formula (I): The anhydrate crystals of the compound represented by formula (I) and / or the hydrate crystals of the compound represented by formula (I) have a moisture content not more than that of the 0.25 hydrate.
2. The hydrate crystal according to claim 1, wherein The water content is less than the water content corresponding to 0.25 hydrate.
3. The hydrate crystal according to claim 2, which has peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 20.0°±0.2°, 20.4°±0.2° and 23.7°±0.2° in a powder X-ray diffraction pattern.
4. The hydrate crystal according to claim 3, which has peaks at diffraction angles (2θ): 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.4±0.2°, 18.4°±0.2°, 19.3°±0.2°, 20.0°±0.2°, 20.4°±0.2°, 21.4°±0.2°, 23.7°±0.2° and 24.1±0.2° in a powder X-ray diffraction pattern. The 0.25 hydrate crystal according to claim 1.
6. The 0.25 hydrate crystal according to claim 5, which has peaks at diffraction angles (2θ): 13.0°±0.2°, 18.4°±0.2°, 19.9°±0.2°, 20.5°±0.2° and 23.7°±0.2° in a powder X-ray diffraction pattern.
7. The 0.25 hydrate crystal according to claim 6, which has peaks at diffraction angles (2θ) of 13.0°±0.2°, 15.5°±0.2°, 16.6°±0.2°, 16.9°±0.2°, 17.5±0.2°, 18.4°±0.2°, 19.2°±0.2°, 19.9°±0.2°, 20.5°±0.2°, 21.5°±0.2°, 23.7°±0.2° and 24.2°±0.2° in its powder X-ray diffraction pattern.
8. The anhydrate crystal according to claim 1, which has peaks at diffraction angles (2θ): 13.1°±0.2°, 18.3°±0.2°, 20.2°±0.2°, 20.5°±0.2° and 23.8°±0.2° in a powder X-ray diffraction pattern.
9. The anhydrate crystal according to claim 8, which has peaks at diffraction angles (2θ) of 13.1°±0.2°, 15.6°±0.2°, 16.7°±0.2°, 17.1±0.2°, 18.3°±0.2°, 19.5°±0.2°, 20.2°±0.2°, 20.5°±0.2°, 21.5°±0.2° and 23.8°±0.2° in a powder X-ray diffraction pattern.
10. The crystal according to claim 1, wherein The crystal is placed in an environment with a temperature of 25° C. and a relative humidity of 35%, and when a powder X-ray diffraction experiment is performed in the same environment, the diffraction angle described in claim 3 or 4 has a peak; The crystal is left to stand at a temperature of 25°C and a relative humidity of 60%, and when a powder X-ray diffraction experiment is conducted under the same environment, the diffraction angle described in claim 6 or 7 has a peak; or When the crystal is left to stand in an environment of a temperature of 50° C. and a relative humidity of 25%, and a powder X-ray diffraction experiment is conducted in the same environment, there is a peak at the diffraction angle described in claim 8 or 9. The crystal according to claim 1 , which has a melting point at 236 to 237° C.
12. A formula (I): The hydrate crystals of the compound represented by have a water content Y (wt %) of 0.0<Y≦1.5 wt %.
13. The crystal according to any one of claims 1 to 12, which has a Raman spectrum at 1448 cm -1 ±2cm -1 、1511cm -1 ±2cm -1 and 2885cm -1 ±2cm -1 Has an absorption peak.
14. A crystal of a compound represented by formula (II), 15 . The crystal according to claim 14 , which has peaks at diffraction angles (2θ): 16.3°±0.2°, 18.4°±0.2°, 20.4°±0.2°, 22.8°±0.2° and 23.9°±0.2° in a powder X-ray diffraction pattern.
16. The crystal according to claim 15, which has peaks at diffraction angles (2θ): 15.1°±0.2°, 16.3°±0.2°, 18.4°±0.2°, 19.2°±0.2°, 20.4°±0.2°, 21.1°±0.2°, 22.0°±0.2°, 22.8°±0.2°, 23.3°±0.2° and 23.9°±0.2° in its powder X-ray diffraction pattern.
17. The crystal according to any one of claims 14 to 16, which has a Raman spectrum at 577 cm -1 ±2cm -1 、612cm -1 ±2cm -1 、740cm -1 ±2cm -1 、1571cm -1 ±2cm -1 and 1718cm -1 ±2cm -1 Has an absorption peak.
Citation Information
Patent Citations
Fused ring derivative having mgat-2 inhibitory activity
WO2019013311A1
Fused-ring derivative having mgat2 inhibitory activity
WO2019013312A1